Label-free detection for colorectal circulating tumor cells - Murdani Abdullah; Annisa Rahmani Putri; Dimas Ramadhian Noor; Muhammad Risyad Fahreza; Anom Bowolaksono; Astari Dwiranti (Tissue and Cell, 2027)

Coconut shell-derived carbon materials via microwave pyrolysis and CO2 activation - Noor Ul Huda Altaf; Muhammad Ayyaz; Lorato Ayalkbet Tekle; Faizan Ahmad; Muhammad Yasin Naz; Yaning Zhang (Biomass and Bioenergy, 2027)

Multi-modal therapeutic approaches to inflammatory bowel disease: plant-derived compounds, nanoparticle drug delivery systems, and gene-based interventions - Arooj Komal; Doua Ilyas; Muhammad Usman Khan; Muhammad Khalil ur Rehman; Tayyaba Hassan; Hina Ayub; Nokhba Naqi; Noor Ullah; Umair Ilyas (Molecular Biology Reports, 2026)

CRIP1 knockdown enhances glycolytic dependence and increases sensitivity to 2-Deoxy-D-Glucose in acute myeloid leukemia - Muhammad Asif Zeb; Faryal Mehwish Awan; Aamir Ali Khan; Sadiq Noor Khan (Molecular Biology Reports, 2026)

High frequency and prognostic significance of TP53 promoter methylation in Pakistani glioblastoma patients - Ahad Naveed; Noor Muhammad; Afshan Khanum; Asif Loya; Muhammad Usman Rashid (Molecular Biology Reports, 2026)

Spatio-temporal distribution patterns and risk assessment of microplastics along a coastal beach in southern Bangladesh - Md. Shawon Hossain; Kowshik Das Karmaker; Mahfujur Rahman; Arnob Ghosh; Swachsa Rahman; Shamiha Shafinaz Shreya; Jarin Tasnim; Mahir Tajwar; Nusrat Jahan Shimu; Mahmud Al Noor Tushar; Mir Shariful Islam; Mohammad Abdul Momin Siddique; et al. (Marine Pollution Bulletin, 2026)

Sustainable postharvest disease management: Integrating biological insights, technological innovations, omics, and precision strategies - Amjad Ali; Shreya Singh; Noor Fatima; Muhammed Tatar; Muhammad Shahbaz (Postharvest Biology and Technology, 2026)

Streptomyces griseoincarnatus AR2 from the cold desert as a biofactory for secondary metabolites with multifaceted bioactivities, confirmed by in vitro and in silico approaches - Arisha Rameen Bhatti; Noor Hassan; Hazrat Ali; Noor ul Huda; Abdul Tawab; Saba Khan; Ambreen Latif; Asad Ali; Waseem Abbas; Iqra Latif Ghuman; Mohsin Khan; Aiman Umar; et al. (Archives of Microbiology, 2026)

Retraction Note: Integrating physiological and molecular insights in cotton under cold stress conditions - Aamir Ali Abro; Muhammad Qasim; Mubashir Abbas; Noor Muhammad; Ijaz Ali; Shiguftah Khalid; Junaid Ahmed; Muhammad Waqas; Sezai Ercisli; Rashid Iqbal; Fang Liu (Genetic Resources and Crop Evolution, 2026)

Nano-formulated β-glucans from Saccharomyces cerevisiae enhance immunity and protection against coccidiosis in broiler chickens - Muhammad Noor; Muhammad Irfan Anwar; Mian Muhammad Awais; Masood Akhtar; Faqir Muhammad (Veterinary Parasitology, 2026)

Identification and functional verification of resistance genes against Lily bulb virus-1 (LbV-1) in Lilium: Insight from sRNA sequencing and transcriptomic profiling - Nisar Uddin; Xia Li; Noor Muhammad; Muhammad Shahid; Adil Hussain; Lili Zhang; Daochen Zhu (Plant Science, 2026)

Engineering MXene-based platforms for electrocatalytic CO2 and N2 reduction reactions; synthesis, modification strategies, and mechanistic insights - Sami Ur Rahman; Saeed Anwar; Awal Noor; Sadaf Qayyum; Yelubay Madeniyet; Niaz Muhammad (Journal of Environmental Chemical Engineering, 2026)

Engineering of novel N-TiO2/P-doped graphene oxide nanocomposite: Mechanistic insights into the photocatalytic removal of benzophenone-3 and H2 production - Wisal Ahmad; Suyeon Jeon; Roman Shah; Dilaram Khan; Syed Izaz Ali Shah; Muhammad Anwar; Raed Al-Juboori; Asad Ali; Noor S. Shah; Javed Ali Khan; Changseok Han (Chemical Engineering Journal, 2026)

Retraction Note: Impact of elevated temperatures on the genetic and morpho-physiological traits of cotton genotypes cultivation - Aamir Ali Abro; Muhammad Qasim; Muhammad Usama Younas; Ijaz Ali; Mubashir Abbas; Noor Muhammad; Shiguftah Khalid; Junaid Ahmed; Umbreen Bibi; Muhammad Waqas; Sezai Ercisli; Fahad Al-Asmari; et al. (Genetic Resources and Crop Evolution, 2026)

Demineralization-assisted porous carbon production from palm oil shell: Enhancing pore accessibility under low-severity conditions for sustainable applications - Arfiana; Era Restu Finalis; Ilhamsyah Noor; Fausiah; Ade Andini; Endro Wahju Tjahjono; Erbert Ferdy Destian; Dorit Bayu Islam Nuswantoro; Herson Bangun; Bagus Alif Firmandoko; Muhammad Dikdik Gumelar; Dita Adi Saputra; et al. (Chemosphere, 2026)

Physiological and molecular mechanisms underlying crop responses to pest attack and their implications for sustainable management - Waseem Ahmed Khattak; Minhas Elahi; Muhammad Anas; Fatima Ijaz; Sania Noor; Javed Iqbal (Physiological and Molecular Plant Pathology, 2026)

Harnessing the biocontrol potential of Trichoderma: Mechanisms, applications, and future prospects in sustainable crop protection - Muhammad Faiq Irfan; Amjad Ali; Rabia Noor; Aniqa Ijaz; Hamza Rafiq; Faisal Shafiq Mirza (Physiological and Molecular Plant Pathology, 2026)

Comparative immune response and disease resistance against Aeromonas hydrophila in Catla catla, Labeo rohita and their intergeneric hybrids - Muhammad Ahmad; Amina Zuberi; Muhammad Noorullah; Zohaib Noor; Waqar Younas; Ajmal Hussain; Muhammad Uzair; Muhammad Kamran (Fish & Shellfish Immunology, 2026)

Retraction notice to “Polyvinyl alcohol and aminated cellulose nanocrystal membranes with improved interfacial compatibility for environmental applications” [Environ. Res. 214 (2022) 113793] - Saleem Ahmad; Zaib Jahan; Farooq Sher; Muhammad Bilal Khan Niazi; Tayyaba Noor; Honghao Hou; Ofaira Azhar; Emina Karahmet Sher (Environmental Research, 2026)

Antibiofilm efficacy and genomic characterization of a lytic bacteriophage targeting MDR uropathogenic Escherichia coli - Muhammad Hassan; Iqbal Ahmad Alvi; Sadiq Noor Khan; Dawood Ahmed; Muhammad Asif; Afshan Saleem; Abdul Jabbar (Archives of Microbiology, 2026)

Mapping Flood Co-Adaptation Strategies in a Vulnerable River Basin: Engaging Youth in Collaborative Decision-Making - Zulfaqar Sa’adi; Zainura Zainon Noor; Nur Syamimi Zaidi; Ee Ling Yong; Fateha Abdul Razak; Nurul Hana Mohamed; Zainab Mat Lazim; Ainul Syarmimi Rosli; Mohd Faiz Foze; Siti Hanna Elias; Khairunnisa Abdul Halim; Muhammad Burhanuddin Bahrodin; et al. (Environmental Management, 2026)

Nitrogen Enhances Leaf–Root Coordination of Hormonal, Redox, and Carbohydrate Metabolism to Improve Drought Tolerance in Calligonum mongolicum Seedlings - Abd Ullah; Akash Tariq; Fanjiang Zeng; Javaria Noor; Muhammad Ahsan Asghar; Jordi Sardans; Josep Peñuelas (Journal of Plant Growth Regulation, 2026)

Large-scale microtremor analysis and lineament mapping for evaluating geological hazards in reservoir-induced seismicity regions: The case history of Kenyir Geopark - Susie Cahyanti Tasman; Neeran Niraj; Muhammad Noor Hisyam Jusoh; Abdul Halim Abdul Latiff; Siti Nur Fathiyah Jamaludin; Muhd Nur Ismail Abdul Rahman; Rudiyanto; Muhammad Afiq Md Ali; Muhamad Zaki Zulkifli; Yuzwan Mohamad; Kee Soo Chen; Fawwaz Azfar Abd Ghafar; et al. (Journal of Applied Geophysics, 2026)

Morphology and phylogeny reveal a New Species and Two New Combinations of Xerocomellus (Boletaceae) from Bajaur, Pakistan - Mohsin Ullah; Malka Saba; Syed Mohammad Tauseeq Ali Shah; Dege Zheng; Umer Rehman; Atika Noor; Muhammad Asif; Dong-Qin Dai; Ishtiaq Ahmad; Samantha C. Karunarathna (Current Microbiology, 2026)

Impacts of infrastructure development on taxonomic and functional diversity of non-volant small mammals - Ummi Nur Syafiqah Daud; Muhammad Iqbal Md. Jamaluddin; Nor Adibah Ismail; Nurfatin Batrisyia Md. Ali; Noor Fatihah Najihah Arazmi; Norfazliyana Nordin; Saiful Hilmi Jamal Shuhaily; Fudzla Zulfa Khiruddin; Amirul Haikal Zainal; Shukor Md. Nor; Aisah Shukor; Mohammad Saiful Mansor (Biodiversity and Conservation, 2026)

Bacillus-derived antimicrobial peptides as alternatives to antibiotics in poultry: mechanisms, applications, and future prospects— a review - Noor Muhammad; Waiza Ansar; Tehmina Bashir; Hubza Ruatt Khan (Archives of Microbiology, 2026)

Exploring ethyl methane sulphonate induced, L-cysteine HCl resistant Bacillus subtilis putative mutant and its immobilization for enhanced acetoin synthesis - Muhammad Usman Ahmad; Sikander Ali; Noor Ul Ain; Nabeera Shahzadi; Maryam Mustaid; Mahwish Arshad; Sadaf Ahmad; Bakar Bin Khatab Abbasi; Ali Irfan; Yousef A. Bin Jardan (Archives of Microbiology, 2026)

The effect of intercropping on soil nutrients and soil organic carbon in an agroforestry system under different climatic conditions: A meta-analysis - Taufiq Bachtiar; Ratih Nurjayati; Veny Rahmawati; Hidawati; Wilda Naily; Rhazista Noviardi; Merri Jayanti; Dyah Marganingrum; Asep Mulyono; Ania Citraresmini; Mieke Rochimi Setiawati; Leons Rixson; et al. (Agroforestry Systems, 2026)

Integrated genomic and physiological insights into the GST gene family in peanut (Arachis hypogaea L.): effects of modified biochar treatments - Muslim Qadir; Noor Muhammad; Rakhwe Kama; Farhan Nabi (Plant and Soil, 2026)

Natural Concurrent Infection by Water Moulds of the Genera Achlya and Protoachlya in a Red Tilapia ( Oreochromis sp.) Hatchery in Malaysia - Mohammad Amirul Faiz Zulkiply; Muhammad Salahudin Kheirel Anuar; Mohd Termizi Yusof; Annas Salleh; Ina Salwany Md Yasin; Channarong Rodkhum; Mohammad Noor Amal Azmai (Journal of Fish Diseases, 2026)
This paper reports a natural concurrent infection by water moulds of the genera Achlya and Protoachlya in a red tilapia hatchery in Malaysia. In December 2024, a mass mortality of cultured juvenile red tilapia was noticed at 7 days after transportation and introduction into a hatchery. The affected fish showed lethargy at the bottom of the tanks, loss of appetite, pale colouration, and were isolated from the schooling group. Further examination found brownish cotton wool‐like growth, particularly at the operculum, gills, and at the base of the fins. Several fish exhibited clinical signs including fin rot, gill inflammation, and cloudy eyes. Histopathological examination of the gills revealed secondary lamella necrosis, fusion, hyperplasia, and infiltration of leucocytes. Morphological and molecular identifications revealed the presence of Achlya bisexualis , A. prolifera , and Protoachlya paradoxa in the diseased fish. These organisms belong to the Oomycetes, a group of fungus‐like protists rather than true fungi. Achlya bisexualis and A. prolifera were more sensitive to salinity, with a minimum inhibitory concentration of 15 ppt, compared to P. paradoxa , which was more halotolerant until 25 ppt. The isolated oomycetes demonstrated the ability to grow at temperatures ranging from 5°C to 30°C, with growth rates increasing with temperature. A cumulative mortality rate of 68% with estimated losses of RM 1000 was recorded from the outbreak, while gradual increases in water salinity up to 20 ppt helped to reduce the mortality. Saprolegniasis poses a significant threat to tilapia's egg and fingerling productions in hatchery operations. However, a synergistic multispecies infection of the pathogens may exacerbate the problem.

Pollution Indices as Useful Tools for Comparative Potential Health Risks of Nickel in Water-Soil-Fodder-Animals Food Chain in Relation to Spatial and Temporal Fluctuations - Hamid Raza; Mukkram Ali Tahir; Noor Us Sabah; Muhammad Imran; Rameez Hussain; Muhammad Tariq (Biological Trace Element Research, 2026)

Comparative genome-wide analysis and characterization of galactinol synthase (GolS) gene family in diploid and tetraploid cotton species - Umm e Abaida Noor; Muhammad Shaban; Muhammad Abubakkar Azmat; Saman Arshad; Abdul Hafeez; Kamran Javed (Biologia, 2026)

From barns to atmosphere: Pakistan's livestock manure-derived NH3, N2O, and CH4 emissions (1961–2022) and cleaner production pathways - Syed Qasim Ali Shah; Noor Haleem; Chaudary Muhammad Haris; Leena Khan; Yousuf Jamal; Humayoun Akram; Xufei Yang (Journal of Cleaner Production, 2026)

Chemical weathering of tropical wetlands in West Kalimantan: Insights from clay mineralogy and major element geochemistry of fluvial surface sediments - Qihuai Wang; Zhifei Liu; Noor Cahyo Dwi Aryanto; Pengfei Ma; Baozhi Lin; Lu Dai; Muhammad Maruf Mukti; Eko Puswanto; Purnama Sendjaja; Hananto Kurnio; Defry Hastria; Hongchao Zhao; et al. (Journal of Asian Earth Sciences, 2026)

Heat-Wave Prediction via Joint Regression and Classification with a Bayesian Deep Bidirectional LSTM Model - Iqra Sardar; Farzana Noor; Muhammad Javed Iqbal; Ishfaq Ahmad; Muhammad Azeem Akbar (Environmental Modelling & Software, 2026)

In vivo systemic toxicity assessment of Bacillus safensis NMCC-189: a probiotic strain evaluated via short-term tolerability and 28-day repeated-dose (OECD 407) study in Balb/c mice - Maryam Khan Sherwani; Syeda Rida Zainab; Jehan Zeb Khan; Shakira Ghazanfar; Fahim Hilal; Rimsha Noor; Muhammad Khalid Tipu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Trends and Disparities in Mortality from Hereditary Ataxia in United States, 2000–2020: A Retrospective Analysis with Projections to 2050 - Muhammad Junaid Iqbal; Fiza Wali; Laraib Israr; Noor Ullah Khan; Hanzala Ahmed Farooqi; Fatima Naveed; Areeba Kabir; Gianluca Morganti; Anastasia Ricci; Michele Menotta (The Cerebellum, 2026)

Developmental Toxicity of Lead and Copper in Chick Embryos: Morphometric and Histological Assessment of In Ovo Exposure - Aima Iram Batool; Noor Fatima; Muhammad Fayyaz Ur Rehman; Naima Huma Naveed; Javaria Ikram; Iram Inayat (Biological Trace Element Research, 2026)

Spatiotemporal distribution of microplastics and associations with river water physicochemical and hydrological parameters, including risk assessments in four tropical rivers in Sarawak, Malaysia - Audrey Primus; Tony Hadibarata; Muhammad Noor Hazwan Bin Jusoh (Environmental Monitoring and Assessment, 2026)
The microplastic pollution of freshwater systems has been a global environmental concern, yet there is a lack of knowledge on tropical rivers. This paper examined the relationships between spatiotemporal microplastic abundance and river water physicochemical and hydrological parameters in the surface water of four rivers of Sarawak in Malaysia (Baram, Miri, Sibuti, and Niah), followed by ecological risk assessment using PLI, PHI, and PERI indices. Surface waters were collected during dry and wet seasons and analyzed using stereomicroscopy and ATR-FTIR spectroscopy. The abundance of microplastics ranged from 6.33 ± 1.53 to 27.67 ± 2.31 items/L. Two-way ANOVA revealed a significant spatial difference ( p < 0.001), but no seasonal difference ( p > 0.05). The microplastics were predominantly fibers, in black, blue, and clear colors, and 100–1000 µm in size. Dominant microplastic polymers were polyethylene and polypropylene. During the dry season, microplastic abundance correlated positively with salinity ( ρ = 0.799) and temperature ( ρ = 0.708) but negatively correlated with pH ( ρ = −0.764). No significant correlations were found in the wet season. PLI values exceeded 1 in all rivers, while PHI values varied among rivers and seasons (7.16–536.46) (Category II: moderate–IV: danger). The presence of high-hazard polymers, such as rubber, elevated polymer-based risks and increased PERI values in some locations. This study provides baseline knowledge on the seasonal effects and anthropogenic pressures on microplastic distribution in tropical rivers in Sarawak, Malaysia.

Dietary sodium propionate enhances growth performance, digestive enzymes, haematology and immunity in Wallago attu - Ayesha Tanveer; Noor Khan; Mahroze Fatima; Hafiz Abdullah Shakir; Ayesha Khizar; Syed Zakir Hussain Shah; Laiba Kareem; Saba Aftab; Malik Muhammad Ramzan; Ahmed Mustafa; Simon John Davies (Journal of Fish Biology, 2026)
Sodium propionate (SP), a short‐chain fatty acid, has been widely used as a feed additive to improve fish growth and health status. The current experiment was designed to investigate the effects of dietary SP on growth, enzymatic activities, haematology and immune status of Wallago attu . Fingerlings (initial weight = 8.80 ± 0.58 g) were fed with graded levels of SP comprising 0.0, 0.5, 1.0, 2.0, 4.0 and 8.0 g/kg levels for 60 days in triplicate glass aquaria (89 × 58 × 61 cm [length × width × depth]). The results showed significant ( p W. attu fingerlings when fed with graded levels of SP. In conclusion, the SP supplementation in W. attu showed best results ranged between 2 and 4 g/kg level by improving fish health and growth performance.

Synergistic Effects of Biochar with Phosphorus Fertilization on soil Biochemical Properties and Wheat Productivity - Nighet Musa; Khalid Saifullah Khan; Muhammad Azeem; Mah-Noor Azad; Mehnoor Khan; Nabeeha Javed; Tajwar Alam (Journal of Soil Science and Plant Nutrition, 2026)

Photocatalytic CO2 reduction: Fundamental principles, mechanistic pathways and material-specific kinetic insights - Syed Izaz Ali Shah; Muhammad Anwar; Wisal Ahmad; Muhammad Ateeq; Amir Zada; Noor S. Shah; Javed Ali Khan; Changseok Han (Chemical Engineering Journal, 2026)

Impact of Various Global Digital Elevation and Crustal Density Models on Accurate Topographic Correction for Geoid Modelling Over East Malaysia - Noorhurul Ain Othman; Muhammad Faiz Pa’suya; Ami Hassan Md Din; Ramazan Alpay Abbak; Mohamad Azril Che Aziz; Chivatsi Jonathan Nyoka; Nurul Shafiqah Hazelin Noor Azmin; Afreena Nisha Mohd Zamri (Pure and Applied Geophysics, 2026)

Critical habitats for sharks and rays in Asia remain largely unprotected - Adriana Gonzalez-Pestana; Peter M. Kyne; Emiliano García-Rodríguez; Ryan Charles; Vanessa Bettcher Brito; Asia O. Armstrong; Amanda Batlle-Morera; Marta D. Palacios; Christoph A. Rohner; Giuseppe Notarbartolo di Sciara; Jo Marie V. Acebes; Serena Adam; et al. (Biodiversity and Conservation, 2026)
The Asia region harbors exceptional chondrichthyan (shark, ray, and chimaera) diversity but faces intense fishing pressure. The Important Shark and Ray Areas (ISRA) process provides a collaborative, evidence-based framework to identify critical habitats and inform spatial management. We assessed ISRAs across the Bay of Bengal, Southeast Asia, and the Northwest Pacific to characterize their extent, ecological significance, and conservation relevance. We delineated 122 ISRAs spanning ~ 1 million km 2 (~ 3% of the region) across 12 jurisdictions and international waters, encompassing habitats for 121 species (~ 30% of Asia’s chondrichthyans), 76% of which are threatened. Depleted taxa (e.g., giant guitarfishes, Glaucostegidae) were represented, but charismatic megafauna (e.g., Whale Shark Rhincodon typus ) were overrepresented. In contrast, deepwater and freshwater species were underrepresented. Reproductive Areas were the most common ISRA sub-criterion applied (52% of ISRAs), largely in nearshore zones, while areas for range-restricted species were less frequently (18%) identified. Twelve ISRAs overlapped with biodiversity hotspots, including seven in areas of high overall chondrichthyan species richness and five in areas of high range-restricted species richness. Citizen science was the predominant research method used to delineate ISRAs, while fisheries data were underused despite the region’s major fisheries footprint. Geographic coverage was uneven: Indonesia held the most ISRAs (n = 40; 71.7% of ISRA coverage) while eight jurisdictions (e.g., Viet Nam, China, Republic of Korea) lacked ISRAs due to data gaps. Protection shortfalls are stark: MPAs cover

Mycoviruses against plant pathogenic fungi: current understanding and future avenues of their potential implication - Fatima Mukhtar; Noor Fatima; Sawera Manzoor; Iqbal Ahmad Alvi; Shafiq ur Rehman; Muhammad Asif (Archives of Microbiology, 2026)

Enhanced Antimicrobial Photodynamic Effect Against Escherichia coli Using MXene-Based Silver–Curcumin 2D Nanocomposite Photosensitizers - Saliha Noor; Shahzad Anwar; Rafaqat Ali Khan; Sawera Malik; Hina Ali; Farwa Nurjis; Shaista Taimur; Muhammad Iftikhar; Muhammad Saleem; Babar Manzoor Atta (Journal of Fluorescence, 2026)

Accumulation of microplastics in mangrove ecosystem: source, properties, and impacts for conservation - Audrey Primus; Tony Hadibarata; Muhammad Noor Hazwan Jusoh (Environmental Sustainability, 2026)
Mangroves, also called blue carbon ecosystems, are crucial as carbon sinks and in climate change mitigation. However, these ecosystems become vulnerable due to plastic pollution, particularly microplastics. A synthesis of studies across Asia, South America, and North America demonstrates that the microplastic contamination in surface waters and sediments is widespread. Fibres and fragments originating from polypropylene (PP) and polyethylene (PE) are prevalent globally, indicating inputs from textile, fishing, and packaging. Seasonal and spatial changes demonstrate greater loads during pre-monsoon periods and in downstream estuaries. The depth-profile analyses indicate that microplastics are buried in mangrove sediment on a long-term basis, supporting their role as long-term sinks. Microplastics have also been found in mangrove species, including fish, crabs, and bivalves, raising concerns about trophic transfer and food security. The accumulation of microplastics is emerging as a factor connected to changes in microbial communities and reduced carbon sequestration potential. Established protocols and policy integration based on mangroves are required to enhance the conservation policies and ensure the ecosystem services.

Adsorptive removal of methylene blue from wastewater using sawdust of Cedrus deodara and its composite with iron oxide nanoparticles: a comparative study - Muhammad Shakeel; Shahid Ali; Muhammad Waseem; Bisma Liaqat; Mahnoor Aurangzeb; Aina Noor; Saira Bibi; Uzma Iqbal; Mehmood-ul-Hassan (Environmental Science and Pollution Research, 2026)

The role of jasmonic acid in enhancing drought resilience in mangroves: from signaling to restoration - Yi Han; Muqadas Noor; Meng Ying Huang; Wenna Wang; Muhammad Anwar; Yanjun Du (South African Journal of Botany, 2026)

Assessment of Coagulansin-A’s therapeutic potential and safety in an ovalbumin (OVA) induced airway inflammation model - Sadaf Naz; Muhammad Usama Mazhar; Aimen Wajid; Rimsha Noor; Lin Zhu; Muhammad Khalid Tipu (Inflammopharmacology, 2026)

Novel design of Fe0-and AC-doped hydroxyapatite-alginate composites for efficient arsenic clean-up: Mechanistic insights from batch and column tests - Behzad Murtaza; Farwah Shamshir; Muhammad Imran; Muhammad Shahid; Kifayat Ullah; Muhammad Nadeem; M. Asif Naeem; Noor Samad Shah; Jianxu Wang; Ajmal Khan; Changseok Han (Journal of Environmental Management, 2026)

Mxene-chitosan composites in wastewater treatment: From adsorption and separation to catalytic remediation - Muhammad Khan; Mohamed Hassan Eisa; Abdul Hameed; Xiaohui Sun; Suleiman M. Suleiman; Muffarih Shah; Noor Majeed; Xiangsheng Chen; Nasir A. Ibrahim; Ashraf A. Qurtam; Katabathini Narasimharao; Zainuriah Hassan (Carbohydrate Polymers, 2026)

Hydroxytyrosol-encapsulated solid lipid nanoparticles mitigate induced arthritis via modulating the cytokines and MMP-13 expression and downregulating oxidative stress in rats - Noor ul Huda; Aftab Ahmad; Muhammad Anjum Zia; Bushra Akhtar (Inflammopharmacology, 2026)

Integrative Molecular and Structural Profiling of Escherichia coli Virulence Genes in Diabetes-Associated Infections - Noor Jahan Begum; Muhammad Qasim; Ihtisham Ul Haq; Hassan Naveed; Farhan Anwar Khan; Zahid Ullah Khan; Farman Ullah Dawar (Current Microbiology, 2026)

Assessing lead toxicity induced alterations in expression of transmembrane metal transporter OsHMA9 and physio-biochemical activities of canola - Khalid Bilal; Nosheen Noor Elahi; Muhammad Imtiaz; Abebe Bogale; Esmael M. Alyami; Norah Hamdi; Tawaf Ali Shah; Ahmad Mohammad Salamatullah (BioMetals, 2026)

Microbial degradation of acetaminophen, a pharmaceutical compound, using the ascomycete fungus Trichoderma asperellum - Upeksha Gayangani Jayasekara; Tony Hadibarata; Muhammad Noor Hazwan Jusoh; Paran Gani; Inn Shi Tan; Adhi Yuniarto; Noorul Hudai Abdullah (Folia Microbiologica, 2026)
The tropical fungus Trichoderma asperellum was identified as a novel acetaminophen degrader, achieving 88.8% removal of 1 g/L acetaminophen in liquid culture under optimal conditions (pH 4.7, 0.55% w/v salinity, 9.7 g/L glucose, and 4.5 g/L peptone). A unique enzyme pattern, predominantly dioxygenase (146 U/mL on day 7), exhibited a degradation mechanism distinct from the ligninolytic enzyme system traditionally associated with fungal biodegradation. The GC-MS analysis has identified some intermediates, including p-aminophenol, 1,3-dihydroxybenzene, phenol, and butenoic acid. At the same time, some of the metabolites have not been reported previously in fungal degradation of acetaminophen. The distinct pattern of enzyme response and the identification of novel intermediates indicate that T. asperellum follows a distinct oxidative hydrolytic route, highlighting its potential as a new fungal candidate for the bioremediation of pharmaceuticals.

Sulfur–regolith composite material for radiation shielding on Mars: A sustainable ISRU approach - Muhammad Nazrif Zamani; Norhazilan Md Noor; Sarehati Umar; Mohamad Shazwan Ahmad Shah; Muhammad Syahir Sarkawi; Asyraf Arif Abu Bakar; Nur Hafizah A. Khalid; Hanis Hazirah Arifin (Journal of Cleaner Production, 2026)

Recent advances in vaccination strategies against acute hepatopancreatic necrosis disease (AHPND) in shrimp for sustainable aquaculture industry: A comprehensive review - Tijani Isa; Riyanto Teguh Widodo; Suzita Mohd Noor; Nur Asyura Nor Amdan; Zulhisyam Abdul Kari; Norhidayah Mohd Taufek; Fathiah Mohamed Zuki; Alias Abdullah; Subha Bhassu; Zarif Mohamed Sofian; Sagir Mustapha; Didi Erwandi Mohamad Haron; et al. (Fish & Shellfish Immunology, 2026)

Antimicrobial Peptides as Next-Generation Disinfectants: Tackling Biocide and Antimicrobial Resistance in Hospital Hygiene – A Narrative Review - Muhammad Umer Asghar; Noor Ul Ain; Muhammad Tariq; Arsalan Haseeb Zaidi (Probiotics and Antimicrobial Proteins, 2026)

Microencapsulation of Probiotics in Polymeric Microgels: Enhanced Viability and Stability through Inorganic Nanoparticle Doping - Muhammad Umar Farooq; Ashok Kumar Bishoyi; Nameer khairullah Mohammed; Suhas Ballal; Abhayveer Singh; Supriya S.; Faiyaz Ahmed; Laraib Shoukat; Noor Akram; Fakhar Islam (Probiotics and Antimicrobial Proteins, 2026)

Quercetin as a promising HIS-C inhibitor and novel therapeutic against antibacterial drug-resistant Acinetobacter baumannii: in vitro and in silico insights - Mohammed Salleh M. Ardawi; Samar A. Badreddine; Muhammad Yasir; Safaa A. Turkistani; Ahmed Afandi; Abdulaziz A. Kimawi; Samah O. Noor; Adhari Alselmi; Salma Mohammed Alsayed; Mada S. Alharthi; Vivek Dhar Dwivedi; Pradeep Sharma; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Nitrogen Addition Optimizes Root-Leaf Coordination of Carbon-Nitrogen Metabolism and Osmolytes to Improve Drought Tolerance in Alhagi Sparsifolia - Abd Ullah; Akash Tariq; Fanjiang Zeng; Muhammad Ahsan Asghar; Javaria Noor; Hafiz Hassan Javed; Abeer Kazmi; Jordi Sardans; Josep Peñuelas (Journal of Soil Science and Plant Nutrition, 2026)

Brassinosteroids: Key Players to Improve Drought Tolerance and Crop Productivity - Muhammad Inzamam-UL-Haq; Imran Khan; Muhammad Umer Chattha; Muhammad Nawaz; Adnan Noor Shah; Sezai Ercişli; Uthman Balgith Algopishi; Fatima M. Abbas; Mohamed Hashem; Muhammad Mahmood Iqbal; Muhammad Umair Hassan (International Journal of Plant Production, 2026)

Sulfur-Coated Urea Improves Rice productivity, Nitrogen Use Efficiency, and Soil Nitrogen Dynamics Under Alternate Wetting and Drying System - Ayesha Mustafa; Imran Khan; Muhammad Umer Chattha; Muhammad Bilal Chattha; Muhammad Nawaz; Adnan Noor Shah; Muhammad Umair Hassan; Uthman Balgith Algopishi; Mohamed Hashem; Sezai Ercişli (International Journal of Plant Production, 2026)

Efficacy of chimeric antigen receptor natural killer cells in treatment of ovarian cancer. A meta-analysis of pre-clinical studies - Nabeel Ahmed; Jawaria Jabeen; Malja Rehman; Safa Noor; Sana Tahseen; Asmaa Qamar; Muhammad Anas; Muhammad Muneeb Khalid; Taseer Ahmad; Weiqun Wang; Lechun Lyu (Immunologic Research, 2026)

Walk, swim and paddle: Qualitative research reframing children's independent mobility through capability and rhythmanalysis - Janatun Naim Yusof; Suzanna Noor Azmy; Noradila Rusli; Muhamad Solehin Fitry Rosley; Nadzirah Hosen; Tengku Intan Suraya Tengku Aziz; Muhammad Farid Azizul Azizui (Journal of Transport Geography, 2026)

Optimizing category-based statistical metrics for selecting global climate models in rainfall projections for Peninsular Malaysia - Zulfaqar Sa’adi; Dauda Pius Awhari; Ricky Anak Kemarau; Zainura Zainon Noor; Zhang Taining; Mohamad Faizal Ahmad; Abdalmaged Salem; Gunarangini Muniandy; Mohammed Faisal Mohammed Dafalla; Wimbi Apriwanda Nursiwan; Muhammad Reza Agraha Maha; Ariani Dwi Astuti; et al. (Theoretical and Applied Climatology, 2026)
Rainfall projections are crucial for climate impact assessments and water resource management, especially in regions like Peninsular Malaysia (PM), where climate variability has a profound effect on socioeconomic and environmental systems. This study aims to optimize category-based statistical metrics, namely, error, efficiency, correlation, composite, and others, to reduce redundancy and identify the most reliable global climate models (GCMs) for improving rainfall projection accuracy in PM. Using CHIRPS daily rainfall data and GCM outputs from the Coupled Model Intercomparison Project Phase 6 (CMIP6), a multi-filtration approach was employed to rank GCM performance based on optimized metrics. The selected metrics span five categories, namely, 7 error metrics, 5 efficiency metrics, 3 correlation metrics, 2 composite metrics, and 5 other metrics, to address a broad range of evaluation needs, ensuring a rigorous and non-redundant assessment of GCMs. A systematic selection of GCM evaluation metrics reduced redundancy by up to 64%, retaining eight key metrics. Principal component analysis (PCA) confirmed these metrics as the most representative, with the first two principal components (PCs) capturing 95.5–100% of the total variance. Using compromise programming index (CPI) and Fisher-Jenks classification, five top-performing GCMs, namely, TaiESM1 (0.5507), CMCC-ESM2 (0.6753), MRI-ESM2-0 (0.7473), CMCC-CM2-SR5 (0.8402), and EC-Earth3-Veg (1.0233), were identified, with TaiESM1 (overlap efficiency, OVL = 0.96) and CMCC-ESM2 (OVL = 0.91) most closely replicating CHIRPS rainfall, making them highly recommended for reliable climate projections. The study concludes that this optimization framework significantly enhances rainfall projection reliability, thereby supporting better-informed decision-making in climate adaptation and water resource planning. Furthermore, the methodology provides a replicable approach for improving GCM selection, particularly in regions with complex climate dynamics, advancing climate modeling for sustainable development planning.

Truncated Variants in FAM20A and WDR72 Genes Underlie Autosomal Recessive Amelogenesis Imperfecta in Four Pakistani Families - Sadaqat Ullah; Sher Alam Khan; Samin Jan; Salah Ud Din; Nazif Muhammad; Zia Ur Rehman; Abid Jan; Muhammad Tariq; Noor Muhammad; Abdul Ghani; Naveed Wasif; Saadullah Khan (Biochemical Genetics, 2026)
Amelogenesis Imperfecta (AI) is a set of hereditary diseases affecting enamel development, leading to various types of enamel defects, potentially impacting oral health unassociated with other generalized defects. AI manifests in syndromic and non-syndromic forms and can be inherited through autosomal recessive, autosomal dominant, or X-linked inheritance patterns. Genetic studies have identified sequence variants in a number of genes (≥ 70) linked to both syndromic and non-syndromic AI, highlighting the genetic diversity underlying the condition. The current study involved clinical evaluation and exome sequencing, aimed at identifying the causative variants in four unrelated consanguineous Pakistani families presenting AI phenotypes. The exome sequencing results revealed a novel homozygous frameshift variant FAM20A : NM_017565.4, c.188dupA; p.(Asp63Glufs*17) in families A, B, and C while a nonsense homozygous variant WDR72 : NM_182758.4, c.2686C > T; p. (Arg896*) in family D. The segregation of both variants was confirmed by Sanger sequencing. Bioinformatics analysis predicted the pathogenicity of these genetic variants. These alterations suggest functional consequences, potentially impairing the FAM20A and WDR72 proteins and causing dental anomalies. This investigation significantly broadens our understanding of FAM20A and WDR72 ’s involvement in AI. Furthermore, this study highlights the genetic heterogeneity of AI (involving FAM20A and WDR72 in this study) within the Pakistani population.

Probiotic-based mycotoxin detoxification in poultry feed: mechanisms, efficacy, challenges, and future directions for sustainable production - Noor Muhammad; Iram Liaqat; Sajida Naseem; Fakhar-un Nisa Yunus; Abid Ali (Archives of Microbiology, 2026)

Copper homeostasis: Crosstalk with plant secondary metabolism and stress responses - Muhammad Tanveer Akhtar; Zhaogeng Lu; Shi-xiong Ren; He-lin Zou; Iqra Noor; Biao Jin (Plant Science, 2026)

Effects of Moringa oleifera and Saccharomyces cerevisiae on growth performance, meat quality, and fatty acids profile of meat in broiler chickens - Noor Ahmad Nastoh; Mustafa Salman; Muhammad Waqas (Tropical Animal Health and Production, 2026)

Pathogenic CDKN2A germline variants are rare in a cohort of unselected pancreatic cancer patients from Pakistan - Shumaila Arif; Noor Muhammad; Humaira Naeemi; Muhammad Usman Rashid (Familial Cancer, 2025)

Adaptability of Barbados Blackbelly rams towards elevated temperature-humidity index assessed through reproductive physiology and behaviour - Muhammad Syafiq Roslan; Mohd Shahmi Hakimi Mazlishah; Noorhidayah Mamat; Nor Azlina Abd Aziz; Noor Hashida Hashim; Nuradilla Mohamad-Fauzi (Small Ruminant Research, 2025)

Sustainable materials for electric vehicle batteries: A comprehensive review of progress, challenges, and opportunities - Noor Hafidzah Jabarullah; Muhammad Saifullah Abu Bakar; Teguh Kurniawan; Asep Bayu Dani Nandiyanto; Asim Laeeq Khan; Fatin Amanina Azis; Muhammad Roil Bilad (Next Research, 2025)

Leveraging green roof technology: Stakeholder analysis of sustainable urban landscape in the developing regions of South Asia - Mehak Shehzad; Adnan Younis; Sabir Aziz; Muhammad Khizar; Noor ul Ain; Muhammad Asad Shabbir (Land Use Policy, 2025)

Ecological resilience of Gallon's curse (Cenchrus biflorus Roxb.) in hyperarid and hypersaline environments - Sana Basharat; Farooq Ahmad; Mansoor Hameed; Zahida Parveen; Muhammad Sajid Aqeel Ahmad; Muhammad Waseem; Ansa Asghar; Sana Fatima; Liu Pingwu; Mehwish Noor; Syed Mohsan Raza Shah; Muhammad Ashraf (Journal of Arid Environments, 2025)

Sexually dimorphic effects of in-utero exposure to a real-life environmental chemical mixture on markers of cardiovascular function in adult sheep - Noor Muhammad Khan; Arpita Vyas; Mohammad Ghasemzadeh-Hasankolaei; Vasantha Padmanabhan; Neil P. Evans; Michelle Bellingham (Environmental Toxicology and Pharmacology, 2025)

Catalyst driven optimization of cogasification and economic evaluation for enriched hydrogen syngas production from lignocellulosic waste toward biorefinery applications - Suhaib Umer Ilyas; Muddasser Inayat; Muhammad Shahbaz; Shaharin A. Sulaiman; Noor A. Merdad; Aymn Abdulrahman (Biomass and Bioenergy, 2025)

Impact of Tannery Effluents on Groundwater Quality and Human Health in Kasur, Pakistan - Mohammad Salman Faisal; Muhammad Awais; Rohina Bashir; Muhammad Bilal Shakoor; Rizwan Aziz; Muhammad Rizwan; Affaq Ali; Simal Akhtar; Noor Fatima (Water, Air, & Soil Pollution, 2025)

Integrating a hybrid statistical Downscaling-based HMM-RF model for enhanced rainfall prediction in Selangor - Noor Hamizah Mohamad Sani; Shazlyn Milleana Shaharudin; Muhammad Safwan Ibrahim; Upmanu Lall; Mou Leong Tan (Stochastic Environmental Research and Risk Assessment, 2025)
Accurate rainfall prediction is crucial for effective weather forecasting and climate modeling. This study aims to assess the effectiveness of a novel hybrid Statistical Downscaling-based Hidden Markov Model-Random Forest Model (SD-based HMM-RF) for rainfall prediction in Selangor, Malaysia. It also examines the best imputation methods for handling missing data, selects predictors for statistical downscaling by reducing dimensionality, and addresses uncertainties in zero-bounded rainfall data. The study utilized observed data (predictand) from 33 rainfall stations and atmospheric data (predictor), covering the period from 2008 to 2018. Seven imputation methods were tested: Mean Imputation (MeI), Median Imputation (MI), Expectation-Maximization (EM) Algorithm, Markov Chain Monte Carlo (MCMC), k-Nearest Neighbor (kNN), Non-iterative Partial Least Square (NIPALS), and Random Forest (RF). Principal Component Analysis (PCA) was used to manage high-dimensional data and select predictors, while HMM was applied to address uncertainties in zero-bounded rainfall data. Five hybrid models: Random Forest (SD-based HMM-RF), Support Vector Machine (SD-based HMM-SVM), Decision Tree (SD-based HMM-DT), k-Nearest Neighbors (SD-based HMM-KNN), and Artificial Neural Networks (SD-based HMM-ANN) were evaluated. Performance metrics, including Root Mean Square Error (RMSE), Mean Absolute Error (MAE), Mean Forecast Error (MFE), Nash-Sutcliffe Efficiency (NSE), Kling-Gupta Efficiency (KGE), and Rank Correlation Coefficient (ρ), were used to identify the most accurate rainfall prediction model. MI emerged as the best-performing method, achieving the lowest RMSE (0.146) and MAE (0.021), along with the highest NSE (1.000) and Pearson correlation coefficient, r (1.000) for all stations. PCA identified five principal components (PC1–PC5) with a cumulative variance of up to 93.254%. HMM analysis determined that three hidden states (K = 3) at iteration 2000 were optimal, with the lowest Bayesian Information Criterion (BIC) of 260,018.30. Among the models, SD-based HMM-RF consistently outperformed others, showing superior accuracy and reliability in rainfall prediction, as indicated by its RMSE (2.298), NSE (0.752), MAE (1.900), near-zero MFE (-0.049), KGE (0.526), and ρ (0.898). By improving rainfall prediction accuracy, the novel hybrid model can enhance early warning systems, inform infrastructure planning, and reduce the economic impact of future flooding events, thereby contributing to more resilient urban development in the region.

Unveiling the spectrum of vancomycin resistance in Staphylococcus aureus from Hospital-acquired urinary tract infections (HA-UTI) in cardiac patients - Muhammad Umer Asghar; Muhammad Tariq; Arsalan Haseeb Zaidi; Kabeer Haneef; Aisha Asghar; Noor Ul Ain (Molecular Biology Reports, 2025)

Indigenous aseel chicken-derived probiotics as biofactories of antifungal metabolites to control mycotoxin contamination in poultry feed - Noor Muhammad; Iram Liaqat; Saiqa Andleeb; Sajida Naseem; Muhammad Arshad; Awais Khalid (Molecular Biology Reports, 2025)

Overexpression of rice High-affinity Potassium Transporter gene OsHKT1;5 improves salinity and drought tolerance in Arabidopsis - Mohammad Asad Ullah; Muhammad-Redha Abdullah-Zawawi; Izreen Izzati Razalli; Noor Liyana Sukiran; Md. Imtiaz Uddin; Zamri Zainal (Molecular Biology Reports, 2025)

Nitrogen Addition Improved Drought Tolerance in Calligonum Mongolicum Via Coordinated Regulation of Osmolytes and Carbon/Nitrogen Metabolism in Leaves and Roots - Abd Ullah; Akash Tariq; Fanjiang Zeng; Javaria Noor; Muhammad Ahsan Asghar; Hafiz Hassan Javed; Abeer Kazmi; Jordi Sardans; Josep Peñuelas (Journal of Soil Science and Plant Nutrition, 2025)

Biochar and Sheep Manure with Reduced Nitrogen Application Increases Rice Productivity and Mitigates N2O Emissions in Paddy Fields - Tahir Abbas Khan; Huang Guoqin; Muhammad Umair Hassan; Mehmood Ali Noor; Muhammad Aamer; Tahani A.Y. Asseri; Rehab O. Elnour (Journal of Soil Science and Plant Nutrition, 2025)

Effect of Fagonia Indica and Garlic Extract On Alternaria Alternata and Post-harvest Quality of Tomato Fruit During Storage - Sameer Lal; Ghulam Khaliq; Abdul Hafeez Mastoi; Asif Irshad; Muhammad Abuzar Jaffar; Lawang Khan; Noor Muhammad (Journal of Crop Health, 2025)

Morpho-palynological evaluation of family Poaceae from arid and semi-arid regions of Pakistan - Bibi Sadia; Mushtaq Ahmad; Wajia Noor; Syed Waseem Gillani; Muhammad Manzoor; Zhiduan Chen; Lixin Zhang; Shazia Sultana; Amir Sohail (Genetic Resources and Crop Evolution, 2025)

Utilization of physicochemical approach to propose a strategy for biofilm inhibition - Ajab Khan; Muhammad Aasim; Noor Shad Bibi; Haris Saddique; Hizb Ullah; Zohaib Khan; Umar Aziz; Nadir Zaman Khan; Waqar Ali; Noor Muhammad (Biofouling, 2025)

Biochar and nano-hydroxyapatite as green adsorbent: synergistic effect in remediating copper-contaminated water and soil - Noor Sharina Mohd Rosli; Rosazlin Abdullah; Jamilah Syafawati Yaacob; Fathiah Mohamed Zuki; Muhammad Irfan Khairul Anuar; Zhi Qi Lim (Environmental Science and Pollution Research, 2025)

Remote sensing technologies for monitoring coral reef health under climate change - Ricky Anak Kemarau; Wee Hin Boo; Nurul Asyiqin Abu Bakar; Zulfaqar Sa'adi; Zaini Sakawi; Muhammad Ammar Fakhry Norzin; Wan Shafrina Wan Mohd Jaafar; Stanley Anak Suab; Oliver Valentine Eboy; Noorashikin Md Noor (Marine Environmental Research, 2025)

Synergistic effect of carbon nanotubes decorated spinel ferrites nanocomposite for robust photocatalytic degradation of persistent environmental pollutants - Sadaf Fatima; Bushra Shaheen; Norah Alomayrah; Noor ul Ain; Muhammad Ibrar; Muhammad Farooq Warsi; Imran Shakir (Journal of Water Process Engineering, 2025)

Systematic review of plant selection in vertical greenery systems for urban sustainability: Current research, knowledge gaps, and future directions - Miktha Farid Alkadri; Aprilia Yolanda; Raisa Putri Alifa; Ricky Purbaya; Dalhar Susanto; Noor Fajrina Farah Istiani; Muhammad Suryanegara (Energy and Buildings, 2025)

Jasmonic Acid: A Key Elicitor of Cold Stress Tolerance in Horticultural Crops - Izhar Ullah; Muhammad Hamza; Noor ul Ain; Heba I. Mohamed; Murad Muhammad; Yaqoob Sultan; Muskan Alam Khan; Abdul Basit (Journal of Plant Growth Regulation, 2025)

Pretreatment with probiotics (Bacillus safensis NMCC-189 and Bacillus clausii) prevents epileptogenesis in mice via modulation of BBB integrity, oxidative stress, and neurotransmitter balance - Maryam Khan Sherwani; Jehan Zeb Khan; Shakira Ghazanfar; Fahim Hilal; Rimsha Noor; Muhammad Khalid Tipu (Inflammopharmacology, 2025)

How likely are high schools to adopt vegetable gardens to combat food insecurity? - Ayesha Noor Fatima; Khurram Yousaf; Muhammad Waqas Alam Chattha (Environment, Development and Sustainability, 2025)

Oral adjuvanted Vibrio vaccine enhances antibody production and lysozyme activity in the serum and mucus of marine-cultured red hybrid tilapia (Oreochromis sp.) against V. harveyi and V. alginolyticus - Tilusha Manchanayake; Aslah Mohamad; Zahaludin Amir-Danial; Nadirah Abu Nor; Chin Yong-Kit; Muhammad Farhan Nazarudin; Roslindawani Md Nor; Qistina Hasnan; Mohd Zamri-Saad; Mohammad Noor Azmai Amal; Md Yasin Ina-Salwany; Annas Salleh (Fish & Shellfish Immunology, 2025)

Comparative Analysis of the Efficiencies of Two Low Cost Adsorbents for Carbon Dioxide Capture - Sayyaf Yousaf; Haris Abdullah Noor; Muhammad Wajid Ullah; Alireza Noorpoor; Adnan Ahmad Tahir; Maria Siddique; Romana Khan (International Journal of Environmental Research, 2025)

Comprehensive Molecular Profiling of AcrAB-TolC Efflux Pump Genes in Salmonella typhi Isolates from Typhoid Infected Patients - Muhammad; Sadiq Azam; Noor Rehman; Alaa S. Alhegaili; Ibrar Khan; Aakash Ahmad; Atif Ali Khan Khalil; Sajid Ali (Current Microbiology, 2025)

A systematic review on the development and efficacy of nano-based vaccine in aquaculture - Shamsu Ibrahim Ishaq; Muhammad Salahudin Kheirel Anuar; Abdulwakil Olawale Saba; Ina Salwany Md Yasin; Che Azurahanim Che Abdullah; Annas Salleh; Muhammad Farhan Nazarudin; Mohd Termizi Yusof; Mohammad Noor Amal Azmai (Aquaculture International, 2025)

Enhanced Photocatalytic Degradation of Methyl Red Dye with Bismuth-Doped ZnO: Kinetics, Mechanistic and Re-cyclability Aspects - Muhammad Alamzeb; Noor-ul-Ain Zulfiqar; Muhammad Faran Akhtar; Iqra Riaz; Faiza Ameen; Aqib Asghar; William N. Setzer (Journal of Fluorescence, 2025)

A metagenomics-based approach to understanding the transmission of healthcare-associated antimicrobial resistance in Pakistan - Muhammad Umer Asghar; Yuting Zhai; Ting Liu; Peixin Fan; Noor Ul Ain; Arsalan Haseeb Zaidi; Muhammad Tariq; Raul C. Mainar-Jaime; Kwangcheol C. Jeong (Journal of Hazardous Materials, 2025)

PpMATE49, a multidrug and toxic compound extrusion transporter, confers manganese toxicity tolerance in peach (Prunus persica) - Kaijie Zhu; Muhammad Ateeq; Xueke Wang; Xue Huang; Jinzhi Yang; Iqra Noor; Guohuai Li; Junwei Liu (Journal of Hazardous Materials, 2025)

Optimized liquid hydrocarbon production via co-pyrolysis of Nypa fronds and polypropylene using fly ash catalyst - Padil Padil; Sunarno Sunarno; Anisa Mutamima; Indra Purnama; Nurfatihayati; Panca Setia Utama; Alhayat Raja Noor; Sunariyo Sunariyo; Muhammad Aziz (Bioresource Technology Reports, 2025)

Multi-centric clinical implementation of the remote and automated quality control programme for digital imaging in Malaysia: challenges and pitfalls - Vinoshah S. Ravichandran; Nur Ammi Hamzah; Li Kuo Tan; Virginia Tsapaki; Olivera Ciraj Bjelac; Noramaliza Mohd Noor; Nur Syahiirah Mohamad Mokhtar; Nur Hasyimah Abd Rashid; Adiela Saiful Fazad; Nur Hafizah Zakaria; Siti Norsyafiqah Mohd Mystafa; Wan Nur Ain Wan Ghazali; et al. (Physical and Engineering Sciences in Medicine, 2025)

Insights into the adsorption of ibuprofen onto polyethylene microplastics using molecular dynamic simulation - Muhammad Ikhwan Nizam; Nurfarwizah Adzuan Hafiz; Mohamed Syazwan Osman; Mohamad Syafiq Abdul Wahab; Lei Wang; Noor Fitrah Abu Bakar; Mohamed Hasaan Hussain; Nur Lina Syahirah Mustapa; Chongqing Wang (Journal of Environmental Management, 2025)

Gum Arabic Organic Coating Maintains Freshness and Modulates Oxidative Stress by Augmenting the Antioxidant Activities of Harvested Ber Fruit - Alisha Noor; Ahmad Sattar Khan; Raheel Anwar; Sajid Ali; Rana Naveed Ur Rehman; Saqib Ayyub; Muhammad Haider Ali (Applied Fruit Science, 2025)

Assessment of some trace elements in African catfish (Clarias gariepinus) from Hadejia-Nguru Wetlands, Northern Nigeria - Musa Alhaji Musa; Dahiru Sani; Abdulwakil Olawale Saba; Mohammad Noor Amal Azmai; Muhammad Farhan Nazarudin; Maimuna Ahmad Amshi (Environmental Monitoring and Assessment, 2025)

A comparative study of fully automatic and semi-automatic methods for oil spill detection using Sentinel-1 data - Muhammad Iqbal Habibie; Hariyanto; Robby Arifandri; Zulfa Qonita; Pronika Kricella; Muh Hisyam Khoirudin; Noor Muhammad Ridha Fuadi; Nurul Shabrina; Nanda Itohasi Gutami; Siti Sadiah; Dewi Kartikasari; Muh.Mulyadi Agus Widodo; et al. (Environmental Monitoring and Assessment, 2025)

A hybrid machine learning-based past performance and envelope approach for rainfall projection in Sarawak, Malaysia - Zulfaqar Sa'adi; Shamsuddin Shahid; Mohammed Sanusi Shiru; Kamal Ahmed; Mahiuddin Alamgir; Mohamad Rajab Houmsi; Lama Nasrallah Houmsi; Zainura Zainon Noor; Muhammad Wafiy Adli Ramli (Urban Climate, 2025)

Talaromyces purpureogenus-mediated mycosynthesis of aluminium oxide nanoparticles and characterization of the physicochemical properties at different calcination temperatures - Muhammad Salahudin Kheirel Anuar; Che Azurahanim Che Abdullah; Muhammad Farhan Nazarudin; Shamsu Ibrahim Ishaq; Mohammad Noor Amal Azmai; Annas Salleh; Ina Salwany Md Yasin; Mohd Termizi Yusof (Fungal Biology, 2025)

Transfersome-based delivery of Muntingia calabura fruit extract for anti-aging applications - Syamsu Nur; Muhammad Fadly Noor Alwani; Fitriyanti Jumaetri Sami; Amriani Sapra; Andi Nur Aisyah; Maulita Indrisari; Nursamsiar; Nurul Arfiyanti Yusuf; Aristianti (Biocatalysis and Agricultural Biotechnology, 2025)

Pharmacological Potential of Holothuria (Mertensiothuria) leucospilota (Brandt, 1835): Antibacterial Activity Against Methicillin-Resistant Staphylococcus aureus and Metabolite Profile - Abdoulie Ceesay; Muhammad Farhan Nazarudin; Norfarrah Mohamed Alipiah; Ina Salwany Md Yasin; Mohammad Noor Azmai Amal; Mohamad Azzam Mohd Sayuti; Intan Safinar Ismail; Mohammed Aliyu-Paiko (Thalassas: An International Journal of Marine Sciences, 2025)

Assessing the Role of Biostimulants in Affecting the Production of Radish and Eggplant - Muhammad Amjad Bashir; Qurat-Ul-Ain Raza; Abdur Rehim; Hafiz Muhammad Ali Raza; Asad Ismail Noor; Mir Sujaul Islam; Faiz-Ul-Hassan; Muhammad Zafar-Ul-Hye; Yucong Geng (Journal of Soil Science and Plant Nutrition, 2025)

Prevalence of Staphylococcus aureus and Antimicrobial Drug Residues in Chicken Liver its Antibiogram Analysis and Implications on Public Health - Gulzar Ahmad; Malik Muhammad Rizwan; Faryal Azam; Muhammad Ijaz; Ainee Urooj Khan; Shamsher Khan; Muhammad Khan; Hafsa Shah; Noor Muhammad; Zia Ur Rahman; Numan Fazal; Sajjad Ullah; et al. (Indian Journal of Microbiology, 2025)

Exploring the morpho-physiological responses of maize to nickel stress modulated by salicylic acid - Atifa Masood; Sumaira Arooj; Muhammad Shahbaz; Noreen Khalid; Muhammad Sajjad; Muhammad Faisal Maqsood; Sunbal Khalil Chaudhari; Abida Abid; Rafia Zainab; Noor Fatima (Cereal Research Communications, 2025)

Multifunctional Magnetic Nanoparticles for Targeted Drug Delivery Against Cancer: A Review of Mechanisms, Applications, Consequences, Limitations, and Tailoring Strategies - Shumaila Riaz; Shaukat Ali; Muhammad Summer; Urva Akhtar; Shehzeen Noor; Rimsha Haqqi; Muhammad Adeel Farooq; Iqra Sardar (Annals of Biomedical Engineering, 2025)

Syringic Acid in Canarium odontophyllum for Diabetes and Obesity – A Review - Gilbert Ringgit; Bo Eng Cheong; Muhammad Dawood Shah; Noor Atiqah Aizan Abdul Kadir; Shafiquzzaman Siddiquee (Cell Biochemistry and Biophysics, 2025)

Academic stress and adolescent health: Exploring eating patterns, dietary preferences, and sleep duration in Pakistan's youth - Zahra Noor; Muniba Khaliq; Azmat Ullah Khan; Muhammad Asif Ali; Sajid Khan Tahir; Kashaf Khaliq (Appetite, 2025)

Trace element removal from wastewater by agricultural biowastes: A data analysis on removal efficacy and optimized conditions - Muhammad Shahid; Sana Khalid; Zeid A. ALOthman; Abdullah A. Al-Kahtani; Irshad Bibi; Rabia Naz; Natasha Natasha; Nabeel Khan Niazi; Jibran Iqbal; Changseok Han; Noor S. Shah; Behzad Murtaza (Science of The Total Environment, 2025)

Uncertainty quantification for variational Bayesian dropout based deep bidirectional LSTM networks - Iqra Sardar; Farzana Noor; Muhammad Javed Iqbal; Ahmed Alsanad; Muhammad Azeem Akbar (Stochastic Environmental Research and Risk Assessment, 2025)

Enhancing defense and production efficiency in rainbow trout (Oncorhynchus mykiss) through prophylactic dietary selenium and vitamin E fortification - Said Jasim Shah; Noor Khan; Mahroze Fatima; Sheeza Bano; Ayesha Tanveer; Sadia Nazir; Muhammad Asghar; Ahmed Mustafa; Maryam Tahir; Saba Aftab; Alex Hing Leung Wan; Simon John Davies (Animal Feed Science and Technology, 2025)

Is There Any Role of Zinc and Copper in Severity and Progression of Osteoarthritis? A Review - Umaima Cheema; Meeram Noor; Hurain Naeem; Mahnoor Arfan; Abdul-Rehman Azam; Shamikha Cheema; Hafiz Muhammad Haris; Muhammad Raza (Biological Trace Element Research, 2025)

Evaluation of genotoxicity and physicochemical variations of Eichhornia crassipes (Mart.) Solms exposed to paper-mill-contaminated wastewater - Harma Shah; Muhammad U. F. Awan; Zahid Mehmood; Noor Sana; Wasim Abbas; Adeel Ahmad; Abdullah Qasim; Annum Gul; Ali Hasnain; Hsi-Hsien Yang (Environmental Monitoring and Assessment, 2025)

Recent advances in recycling and upcycling of hazardous plastic waste: A review - Siti Zulaika Khairul Anuar; Abu Hassan Nordin; Siti Muhamad Nur Husna; Abdul Hafidz Yusoff; Syafikah Huda Paiman; Siti Fadilla Md Noor; Muhammad Luqman Nordin; Siti Nurlia Ali; Ya Mohammad Nazir Syah Ismail (Journal of Environmental Management, 2025)

Boosted proton conduction in LAO electrolyte through Li segregation for High-Performance ceramic fuel cells - Nabeela Akbar; Muhammad Yousaf; M.A.K. Yousaf Shah; Jahangeer Ahmed; Asma Noor; Quazi Arif Islam; Yan Wu; Saad M. Alshehri; Naveed Mushtaq; Bin Zhu; Sara Paydar (Fuel, 2025)

Sexually dimorphic cardiovascular impacts of prenatal exposure to a real-life environmental chemical mixture in adult offspring - Noor Muhammad Khan; Victoria Scott; Mohammad Ghasemzadeh-Hasankolaei; Vasantha Padmanabhan; Arpita Vyas; Neil P. Evans; Michelle Bellingham (Environmental Toxicology and Pharmacology, 2025)

Optimization and partial purification of tannase from Bacillus licheniformis AS1 under submerged fermentation and its application - Aqsa Shafique; Hafiz Abdullah Shakir; Muhammad Irfan; Shaukat Ali; Muhammad Khan; Chaman Ara; Noor Khan (Systems Microbiology and Biomanufacturing, 2025)

Therapeutic Role of Probiotics Against Environmental-Induced Hepatotoxicity: Mechanisms, Clinical Perspectives, Limitations, and Future - Shehzeen Noor; Shaukat Ali; Muhammad Summer; Anfah Riaz; Laiba Nazakat; Aqsa (Probiotics and Antimicrobial Proteins, 2025)

Flood characteristics and risk analysis in small watersheds on the Loess Plateau under extreme heavy rainfall - Muhammad Imran; Jingming Hou; Tian Wang; Qingshi Zhou; Donglai Li; Majid Habib Khan; Irfan Ullah; Rana Shahzad Noor; Muhammad Umair; Shakeel Hussain (Natural Hazards, 2025)

Pharmacological modes of plant-derived compounds for targeting inflammation in rheumatoid arthritis: A comprehensive review on immunomodulatory perspective - Laiba Nazakat; Shaukat Ali; Muhammad Summer; Fakiha Nazakat; Shehzeen Noor; Anfah Riaz (Inflammopharmacology, 2025)

Tracking the tropical aquatic dragon: environmental DNA (eDNA) detection for monitoring the endangered Asian arowana, Scleropages formosus (Müller and Schlegel, 1840) - Norli Fauzani Mohd Abu Hassan Alshari; Muhammad Hanif Iryani Adnan; Danial Hariz Zainal Abidin; Siti Zafirah Ghazali; Min Pau Tan; Noor Adelyna Mohammed Akib; Sébastien Lavoué; Siti Azizah Mohd Nor (Hydrobiologia, 2025)

Fish oil replacement with linseed oil affects growth, tissue fatty acid composition, blood chemistry, and antioxidant biomarkers in rohu, Labeo rohita - Muhammad Asghar; Noor Khan; Mahroze Fatima; Seyda Tacer-Tanas; Simon John Davies; Naveed ul Haque; Ayesha Tanveer; Murat Arslan (Aquaculture International, 2025)

The potential of hydrolyzed chicken feather meal as a partial replacement for fish meal and its effects on the growth and health status of African catfish (Clarias gariepinus) fingerlings - Nik Nur Akmal ‘Aliah Abdul Rashid; Zulhisyam Abdul Kari; Parashuram Kallem; Suniza Anis Mohamad Sukri; Syed Muhammad Al-Amsyar; Noor Khalidah Abdul Hamid; Muhammad Anamul Kabir; El-Sayed Hemdan Eissa; Martina Irwan Khoo; Krishnakumar Velayudhannair; Ajay Guru (Aquaculture International, 2025)

Microplastic accumulation in respiratory and digestive systems of selected fish from Banten Bay, Indonesia - Sri Yuningsih Noor; Etty Riani; Sigid Hariyadi; Nurlisa Alias Butet; Muhammad Reza Cordova (Environmental Monitoring and Assessment, 2025)

Integrating industry 4.0 for enhanced sustainability: Pathways and prospects - M. Imran Khan; Tabassam Yasmeen; Mushtaq Khan; Noor Ul Hadi; Muhammad Asif; Muhammad Farooq; Sami G. Al-Ghamdi (Sustainable Production and Consumption, 2025)

Advancements in metal selenide nanocomposites for efficient photocatalytic water splitting applications - Zeshan Ali Sandhu; Soha Ghaffar; Muhammad Asam Raza; Noor ul Huda; Sufyan Ashraf; Umair Talat; Areej Chauhdary; Hamza Gulzarab; Abdullah G. Al-Sehemi (Fuel, 2025)

Role of artificial intelligence in halal authentication and traceability: A concurrent review - Asad Nawaz; Atka Afzal; Ali Khatibi; Amar Shankar; Heena Madan; Hafiza Sana Faisal; Amna Shahbaz; Ifrah Usman; Nimra Zulfiqar; Farhan Saeed; Aftab Ahmed; Ali Imran; et al. (Food Control, 2025)

Visible light active CdS/CuO nanocomposites for photocatalytic degradation of ciprofloxacin, H2 production and antimicrobial activity - Naveed Akhtar; Chaejin Choi; Muhammad Ateeq; Perveen Fazil; Noor S. Shah; Javed Ali Khan; Abdullah G. Al-Sehemi; Amir Zada; Muhammad Ishaq Ali Shah; Rabia Ikram; Changseok Han (Chemical Engineering Journal, 2025)

Role of Melatonin in Leaf Gas Exchange by Redox Regulation, K+ Homeostasis and Gene Expression in Canola Under Salinity Stress - Muhammad Ali; Muhammad Farooq; Adnan Noor Shah; Ghulam Hassan Abbasi; Salman Ahmad; Aasma Parveen; Birhanu Iticha; Muhammad Riaz; Muhammad Kamran; Fatima Nisar (Journal of Soil Science and Plant Nutrition, 2025)

The Collaborative Role of the Regulatory (MYB-bHLH-WD40) and Structural Genes Results in Fruit Coloration in Plants Some Do This Under the Influence of External Stimuli - Noor Muhammad; Zhi Luo; Zhiguo Liu; Mengjun Liu (Journal of Plant Growth Regulation, 2025)

Seismic capacity assessment of eco-friendly fly ash brick masonry structures after retrofitting - Shah Zeb; Khan Shahzada; Umar Ahmad Noor; Muhammad Adeel Arshad; Abdur Rahim Khan; Haleem Ullah Khan (Innovative Infrastructure Solutions, 2025)

Recent developments in mitigating clogging in permeable pavements: a state-of-the-art review - Taqia Rahman; Anissa Noor Tajudin; Adhin Harum Wulaningtyas; Neil Andika; Muhammad Zudhy Irawan; Iswandaru Widyatmoko (Innovative Infrastructure Solutions, 2025)

Integrating physiological and molecular insights in cotton under cold stress conditions - Aamir Ali Abro; Muhammad Qasim; Mubashir Abbas; Noor Muhammad; Ijaz Ali; Shiguftah Khalid; Junaid Ahmed; Muhammad Waqas; Sezai Ercisli; Rashid Iqbal; Fang Liu (Genetic Resources and Crop Evolution, 2025)

RETRACTED ARTICLE: Impact of elevated temperatures on the genetic and morpho-physiological traits of cotton genotypes cultivation - Aamir Ali Abro; Muhammad Qasim; Muhammad Usama Younas; Ijaz Ali; Mubashir Abbas; Noor Muhammad; Shiguftah Khalid; Junaid Ahmed; Umbreen Bibi; Muhammad Waqas; Sezai Ercisli; Fahad Al-Asmari; et al. (Genetic Resources and Crop Evolution, 2025)

Exploring the diversity of scorpions in Lahore Division, Punjab: an ecological approach - Muhammad Mohsin Ahsan; Abdul Khalaq; Hafiz Muhammad Tahir; Muhammad Ismail; Muhammad Samiullah; Maira Noor; Safia Bibi (International Journal of Tropical Insect Science, 2025)

Impact of silicon nitride nanoparticles on soil organic carbon dynamics in subtropical evergreen forest ecosystems of China: An incubation study - Fasih Ullah Haider; Ahmad Latif Virk; Shuyidan Zhou; Noor ul Ain; Luis Carlos Ramos Aguila; Kadambot H.M. Siddique; Muhammad Farooq; Yuelin Li (Science of The Total Environment, 2025)

A global review on perfluoroalkyl acids (PFAAs) in the riverine systems: Environmental behaviours and risks implications - Muhammad Younas; Kifayatullah Khan; Maria Zeb; Muhammad Yaseen; Noor Samad Shah; Hassan Alshemmari; Yasar N. Kavil; Saeed Saad Alelyani; Mohamed Hussien; Sidra Zeb; Di Du (Science of The Total Environment, 2025)

Maximizing heavy metal removal and precious metal recovery with innovative biowaste-derived biosorbents and biochar - Behzad Murtaza; Roshina Arshad; Moon Kinza; Jianxu Wang; Muhammad Shahid; Muhammad Imran; Noor S. Shah; Qasim Ali; Jibran Iqbal; Changseok Han (Process Safety and Environmental Protection, 2025)

Bio-templating approach and DFT study of ZrMo@KIT-6 catalyst for the conversion of deep fried oil into sustainable biodiesel production - Muhammad Noman; Muhammad Farooq; Anita Ramli; Ghazala Abid; Fouzia Perveen; Dur Muhammad; Rida Ihsan; Faizan Jamil; Ali Raza Ayub; Noor Saeed khattak; Ata Ur Rahman (Fuel, 2025)

Genome and transcriptome-based characterization of cytochrome P450 (CYP) monooxygenase superfamily gene and the key role of ZjCYP98A9a-89 in flavonoid biosynthesis during fruit development of jujube (Ziziphus jujuba Mill.) - Noor Muhammad; Yao Liu; Zhiguo Liu; Lixin Wang; Minsheng Yang; Mengjun Liu (Food Bioscience, 2025)

Simultaneous alleviation of antimony toxicity in rice and in-Vitro bio-accessibility by using biochar and seaweed based fertilizer blend - Muhammad Umair Hassan; Huang Guoqin; Muhammad Nawaz; Adnan Noor Shah; Shujuan Li; Tahir Abbas Khan; Khalid Mashay Al-Anazi; Mehmood Ali Noor; Adnan Rasheed; Xu Huifang; Sezai Ercisli (Environmental Pollution, 2025)

Ocean-atmosphere interrelation of Bjerknes feedback loop associated with Indian Ocean Dipole retrieved from altimeter radar and microwave radiometer of satellite altimetry - Noor Nabilah Abdullah; Dudy Darmawan Wijaya; Irwan Meilano; Wedyanto Kuntjoro; Zamzam Akhmad Jamaluddin Tanuwijaya; Muhammad Rais Abdillah; Fathin Nurzaman (International Journal of Remote Sensing, 2025)

Intermittent Fasting and Probiotics: Synergistic Modulation of Gut Health for Therapeutic Advantages - Amna Shehbaz; Muhammad Afzaal; Noor Akram; Farhan Saeed; Warda Khan; Faiyaz Ahmed; Aftab Ahmed; Aasma Asghar; Zargham Faisal (Probiotics and Antimicrobial Proteins, 2025)

De novo transcriptome analysis and gene expression profiling of Conticribra weissflogii during low salinity reveals regulation of fatty acid biosynthesis genes - Muhammad Faiz Zakaria; Ahmad Hanafi Ahmad Kamal; Noor Amanina Awang; Nor Afiqah-Aleng; Kamariah Bakar; Noorul Darlina Edlin Abd Rahim; Hock-Seng Tan; Mohd Effendy Abd Wahid; Ghows Azzam; Malinna Jusoh (Journal of Applied Phycology, 2025)

Multi-scale computational modeling to identify novel chemical scaffolds as trehalose-6-phosphate phosphatase inhibitors to combat Burkholderia pseudomallei - Sara Noor; Mohammad Abdullah Aljasir; Maryam Bashir; Kalsoom Khan; Sajjad Ahmad; Syed Ainul Abideen; Saifullah Khan; Farhan Siddique; Hamza Ahmad; Khudija Ghani; Madiha Iqbal; Muhammad Irfan; et al. (In Silico Pharmacology, 2025)

Elucidation of synbiotic diet comprising of Lactobacillus plantarum L20 and Sargassum polycystum on gastrointestinal microbiota, tissue structures and AHPND associated dysbiosis susceptibility in black tiger shrimp (Penaeus monodon) - Yong Kit Chin; Mohamad Azzam-Sayuti; Aslah Mohamad; Wan Omar Haifa-Haryani; Mohd Ihsanuddin Ahmad; Muhammad Farhan Nazarudin; Nur Shidaa Mohd Ali; Md Yasin Ida-Muryany; Murni Marlina Abd Karim; Salleh Annas; Mohd Nor Norhariani; Mohammad Noor Azmai Amal; et al. (Aquaculture, 2025)

QUAL2K water quality model: A comprehensive review of its applications, and limitations - Siti Salwa Mohamad Noor; Noor Aida Saad; Muhammad Fitri Mohd Akhir; Muhamad Syafiq Abd Rahim (Environmental Modelling & Software, 2025)

Taxonomic significance of palyno-morphic markers for the delimitation of some Brassicaceous taxa in Balochistan Province (Pakistan) - Wajia Noor; Muhammad Zafar; Mushtaq Ahmad; Bibi Sadia; Syed Waseem Gillani; Muhammad Manzoor; Maria Ameen (Genetic Resources and Crop Evolution, 2025)

Taxonomic implications of petiole microanatomical traits among Asteraceae tribes from arid–semiarid regions of Baluchistan, Pakistan - Bibi Sadia; Mushtaq Ahmad; Muhammad Zafar; Wajia Noor; Muhammad Manzoor; Syed Waseem Gillani; Shazia Sultana (Genetic Resources and Crop Evolution, 2025)

From stress to resilience: Unraveling the molecular mechanisms of cadmium toxicity, detoxification and tolerance in plants - Iqra Noor; Hamza Sohail; Muhammad Tanveer Akhtar; Jiawen Cui; Zhaogeng Lu; Salma Mostafa; Mirza Hasanuzzaman; Sajjad Hussain; Nan Guo; Biao Jin (Science of The Total Environment, 2024)

Removal of ammonia from rubber wastewater using rubber-sludge-based biochar to enhance biogas production - NurulEzza Fazlina Abu; Noor Yahida Yahya; Fatin Zafirah Mansur; Nurmunira Muhammad (Process Safety and Environmental Protection, 2024)

Adaptive mechanisms of wheat cultivars to lead toxicity through enhanced oxidative defense, ionomic redistribution, and anatomical modifications - Muhammad Anas; Muhammad Saad Bashir; Khadija Saleem; Atika Noor; Umar Masood Quraishi (Journal of Plant Physiology, 2024)

Identification of novel antimicrobial compounds in colostrum-associated Lactiplantibacillus plantarum ZFS 1 and 2 by integrating in vitro, machine learning and bioinformatics approaches - Zainab Fiaz; Fatima Noor; Aqsa Ikram; Talha Ali Chohan; Muhammad Zubair Aslam; Najma Arshad (Food Bioscience, 2024)

Prevalence and associated risk factors of Brucella abortus and Brucella melitensis in humans and cattle populations: A comprehensive study - Ihsan Ullah; Shumaila Naz; Umer Sadique Khattak; Muhammad Saeed; Noor ul Akbar; Sania Rauf (Comparative Immunology, Microbiology and Infectious Diseases, 2024)

Molecular prevalence, phylogenetic analysis, and PCR-based detection of Brucella melitensis in humans and cattle in Southern Khyber Pakhtunkhwa, Pakistan - Ihsan Ullah; Shumaila Naz; Umer Sadique Khattak; Muhammad Saeed; Noor ul Akbar; Sania Rauf (Comparative Immunology, Microbiology and Infectious Diseases, 2024)

Advances in agar-based composites: A comprehensive review - Muffarih Shah; Abdul Hameed; Muhammad Kashif; Noor Majeed; Javariya Muhammad; Nasrullah Shah; Touseef Rehan; Abbas Khan; Jalal Uddin; Ajmal Khan; Hamdy Kashtoh (Carbohydrate Polymers, 2024)

Zebrafish as an innovative model for exploring cardiovascular disease induction mechanisms and novel therapeutic interventions: a molecular insight - Shaukat Ali; Maryam Zulfiqar; Muhammad Summer; Mahnoor Arshad; Shehzeen Noor; Laiba Nazakat; Abdullah Javed (Molecular Biology Reports, 2024)

Pharmacological and immunomodulatory modes of action of medically important phytochemicals against arthritis: A molecular insight - Aqsa; Shaukat Ali; Muhammad Summer; Saima Yousaf; Laiba Nazakat; Shehzeen Noor (Molecular Biology Reports, 2024)

Predominance of MGMT promoter methylation among Pakistani glioblastoma patients - Noor Muhammad; Samir Fasih; Bilal Malik; Shahid Hameed; Asif Loya; Muhammad Usman Rashid (Molecular Biology Reports, 2024)

Effect of green synthesized silver nanoparticles on growth and physiological responses of pearl millet under salinity stress - Zakir Ullah; Syed Inzimam Ul Haq; Abd Ullah; Muhammad Ahsan Asghar; Mahmoud F. Seleiman; Khansa Saleem; Fanjiang Zeng; Noor Us Sama; Khalid Kamran; Sheraz Ahmad (Environment, Development and Sustainability, 2024)

Innovative strategies for characterizing and managing huanglongbing in citrus - Mustansar Mubeen; Amjad Ali; Yasir Iftikhar; Muhammad Shahbaz; Muhammad Irfan Ullah; Md. Arshad Ali; Noor Fatima; Jaya Seelan Sathiya Seelan; Yee Shin Tan; Uthman Balgith Algopishi (World Journal of Microbiology and Biotechnology, 2024)

RNA interference: a promising biotechnological approach to combat plant pathogens, mechanism and future prospects - Amjad Ali; Muhammad Shahbaz; Fatih Ölmez; Noor Fatima; Ummad Ud Din Umar; Md. Arshad Ali; Muhammad Akram; Jaya Seelan Sathiya Seelan; Faheem Shehzad Baloch (World Journal of Microbiology and Biotechnology, 2024)

Using citizen science data to uncover the invasion of the non-native fish, Hemibagrus wyckioides (Fang and Chaux, 1949) in Peninsular Malaysia - Mohamad Aqmal-Naser; Intan-Faraha A. Ghani; Muhammad Rasul Abdullah Halim; Muhammad Fahmi-Ahmad; Md. Zain Khaironizam; Mohammad Noor Azmai Amal; Zahar Azuar Zakaria; Mohd Lokman Ilham-Norhakim; Amirrudin B. Ahmad (Biological Invasions, 2024)

Multifaceted roles of zinc nanoparticles in alleviating heavy metal toxicity in plants: a comprehensive review and future perspectives - Muhammad Umair Hassan; Huang Guoqin; Naeem Ahmad; Tahir Abbas Khan; Muhammad Nawaz; Adnan Noor Shah; Adnan Rasheed; Tahani A. Y. Asseri; Sezai Ercisli (Environmental Science and Pollution Research, 2024)

Bovine colostrum: Therapeutic potential and clinical evidence - Talha Shireen Khan; Noor Akram; Zargham Faisal; Farhan Saeed; Amara Rasheed; Faiyaz Ahmed; Muhammad Afzaal (International Dairy Journal, 2024)

Deciphering fungicide resistance in Phytophthora: mechanisms, prevalence, and sustainable management approaches - Syed Atif Hasan Naqvi; Muhammad Farhan; Muhammad Ahmad; Rafia Kiran; Noor Fatima; Muhammad Shahbaz; Muhammad Akram; Jaya Seelan Sathiya Seelan; Amjad Ali; Salman Ahmad (World Journal of Microbiology and Biotechnology, 2024)

The underlying molecular mechanisms of hormonal regulation of fruit color in fruit-bearing plants - Noor Muhammad; Zhiguo Liu; Lixin Wang; Minsheng Yang; Mengjun Liu (Plant Molecular Biology, 2024)

Smoothed particle hydrodynamics simulation of debris flow on deposition area - Muhammad Khairi A. Wahab; Mohd Remy Rozainy Mohd Arif Zainol; Jazaul Ikhsan; Mohd Hafiz Zawawi; Mohamad Aizat Abas; Norazian Mohamed Noor; Norizham Abdul Razak; Neeraj Bhardwaj; Siti Multazimah Mohamad Faudzi (Natural Hazards, 2024)

Genetic Association Among Morpho-Physiological Attributes Against Heat Tolerance in Rice Genotypes - Hafiz Ghulam Muhu-Din Ahmed; Noor Fatima; Yawen Zeng; Muddassir Hussain; Muhammad Moaaz Mushtaq; Ghulam Sabir Hussain; Muhammad Irfan Akram; Amjad Saeed; Adnan Noor Shah; Hayssam M. Ali; Mohamed M. A. Abdelhamid; Sezai Ercisli (Journal of Crop Health, 2024)

Exploring the underlying pharmacological, immunomodulatory, and anti-inflammatory mechanisms of phytochemicals against wounds: a molecular insight - Anfah Riaz; Shaukat Ali; Muhammad Summer; Shehzeen Noor; Laiba Nazakat; Aqsa; Muhammad Sharjeel (Inflammopharmacology, 2024)

Temporal assessment of forest cover dynamics in response to forest fires and other environmental impacts using AI - Shehla Noor; Rafia Mumtaz; Muhammad Ajmal Khan (Environmental Monitoring and Assessment, 2024)

Nanomedicine: Patuletin-conjugated with zinc oxide exhibit potent effects against Gram-negative and Gram-positive bacterial pathogens - Naveed Ahmed Khan; Adeelah Alvi; Saif Alqassim; Noor Akbar; Bushra Khatoon; Muhammad Kawish; Shaheen Faizi; Muhammad Raza Shah; Bader S. Alawfi; Ruqaiyyah Siddiqui (BioMetals, 2024)

Role of Phytobiotics in Modulating Transcriptomic Profile in Carps: A Mini-Review - Lee Seong Wei; Guillermo Téllez-Isaías; Zulhisyam Abdul Kari; Albaris B. Tahiluddin; Wendy Wee; Muhammad Anamul Kabir; Noor Khalidah Abdul Hamid; Romalee Cheadoloh (Biochemical Genetics, 2024)

Growth, body composition, lipid profile, and peroxidation, physiological stress, and blood metabolic indicators in Labeo rohita fed a fish oil replacement with blended linseed and sunflower oils - Muhammad Asghar; Noor Khan; Mahroze Fatima; Murat Arslan; Simon John Davies; Naveed ul Haque (Aquaculture International, 2024)

Recent advancements of nanotechnology in fish aquaculture: an updated mechanistic insight from disease management, growth to toxicity - Muhammad Sharjeel; Shaukat Ali; Muhammad Summer; Shehzeen Noor; Laiba Nazakat (Aquaculture International, 2024)

Inflammatory response of nanoparticles: Mechanisms, consequences, and strategies for mitigation - Muhammad Summer; Rimsha Ashraf; Shaukat Ali; Horacio Bach; Shehzeen Noor; Qudsia Noor; Saima Riaz; Rana Rashad Mahmood Khan (Chemosphere, 2024)

Managing antimony pollution: Insights into Soil–Plant system dynamics and remediation Strategies - Fasih Ullah Haider; Usman Zulfiqar; Noor ul Ain; Tariq Mehmood; Umed Ali; Luis Carlos Ramos Aguila; Yuelin Li; Kadambot H.M. Siddique; Muhammad Farooq (Chemosphere, 2024)

The feasibility of in-situ resource utilisation binder systems for construction materials on Mars: A review - Muhammad Nazrif Zamani; Mohamad Shazwan Ahmad Shah; Sarehati Umar; Nordin Yahaya; Nurul ‘Azizah Mukhlas; Jang Ho-Jay Kim; Norhazilan Md Noor (Advances in Space Research, 2024)

In vivo assessment of Lactobacillus plantarum strains in black tiger shrimp (Penaeus monodon): implications for growth performance, probiotic-pathogen interaction, and defense against AHPND infection - Yong Kit Chin; Wan Omar Haifa-Haryani; Muhammad Farhan Nazarudin; Mohd Ihsanuddin Ahmad; Mohamad Azzam-Sayuti; Nur Shidda Mohd Ali; Mohamad Syazwan Ngalimat; Aslah Mohamad; Md Yasin Ida-Muryany; Murni Karim; Annas Salleh; Mohd Nor Norhariani; et al. (Aquaculture International, 2024)

Insight into mechanism of excellent visible-light photocatalytic activity of CuO/MgO/ZnO nanocomposite for advanced solution of environmental remediation - Muhammad Imran; Mohsin Raza; Hadia Noor; Sadia Muniza Faraz; Ali Raza; Umar Farooq; Mohammad Ehtisham Khan; Syed Kashif Ali; Omer Y. Bakather; Wahid Ali; Abdullateef H. Bashiri; Waleed Zakri (Chemosphere, 2024)

2030 oil palm plantation carbon footprint estimation using O-LCA and forecasting - Farizal F; Trisha Amanda; Muhammad Dachyar; Zainura Zainon Noor (Journal of Cleaner Production, 2024)

Response of cotton mealybug, Phenacoccus Solenopsis Tinsley (Sternorrhyncha: Pseudococcidae) to predators, neem oil, and synthetic insecticide under semi-field and field conditions - Muhammad Mamoon-ur-Rashid; Khalid Abdullah; Habib Ali; Muhammad Tariq; Adnan Noor Shah; Shahbaz Ali (International Journal of Tropical Insect Science, 2024)

Population exposure to emerging perfluoroalkyl acids (PFAAs) via drinking water resources: Application of multivariate statistics and risk assessment models - Kifayatullah Khan; Muhammad Younas; Jafar Ali; Noor Samad Shah; Yasar N. Kavil; Mohammed A. Assiri; Xianghui Cao; Hassan Sher; Afsheen Maryam; Yunqiao Zhou; Muhammad Yaseen; Li Xu (Marine Pollution Bulletin, 2024)

Optimizing refuse-derived fuel production from scheduled wastes through Aspen plus simulation - Muhammad Afiq Zubir; Hesam Kamyab; Yasser Vasseghian; Haslenda Hashim; Ong Mei Zhi; Sameer Rajaratnam Abdullah; Mohammad Yusuf; Balasubramaniam Kapran; Afif Hamidi Kori; Noor Shawal Nasri; Hien Y Hoang (Environmental Research, 2024)

Efficacy of Different Pre and Post Emergence Herbicide Application on Late Sown Maize Crop Under Variable Planting Density - Muhammad Talha Aslam; Rizwan Maqbool; Imran Khan; Muhammad Umer Chattha; Muhammad Nawaz; Adnan Noor Shah; Muhammad Zia Ul Haq; Muhammad Nauman Gulzar; Fatmah M. Alqahtani; Mohamed Hashem; Muhammad Umair Hassan; Sezai Ercisli (International Journal of Plant Production, 2024)

Hollow CoP/carbon as an efficient catalyst for the peroxymonosulfate activation derived from phytic acid assisted metal-organic framework - Muhammad Abdul Nasir Khan; Prosper Kwame Klu; Chengming Xiao; Junwen Qi; Tayyaba Noor; Zeshan Sheikh; Kaleemullah Kalwar; Jiansheng Li (Chemosphere, 2024)

Trapping the genetic variation for yield and yield related attributes in bread wheat under water deficit stress - Hafiz Ghulam Muhu-Din Ahmed; Muhammad Naeem; Yawen Zeng; Aziz Ullah; Ghulam Sabir Hussain; Muhammad Irfan Akram; Amjad Saeed; Noor Fatima; Ibtasam Moeez; Hayssam M. Ali; Nagy S. Radwan; Sezai Ercisli; et al. (Euphytica, 2024)

Toxicological profile and potential health concerns through metals and trace elements exposure in brick kiln workers from Lahore, Pakistan - Talha Saeed; Naeem Akhtar Abbasi; Muhammad Talha Zahid; Noor Fatima; Kaleem Ullah; Muhammad Fahim Khokhar (Environmental Geochemistry and Health, 2024)

Morphological and molecular characterisation of Cymothoa eremita (Brunnich, 1783) (Isopoda: Cymothoidae) from the South China Sea - Melissa Beata Martin; Muhammad Adam Mohamed Yusoff; Noor Syazwaney Hashim; Thinh Dinh Do; Nakisah Mat Amin; Faizah Shaharom-Harrison; Yeong Yik Sung; Wang Min; Liang Yantao; Md Asaduzzaman; Li Lian Wong (Regional Studies in Marine Science, 2024)

Heritability and Genotypic Association Among Seedling Attribute Against Salinity Stress Tolerance in Wheat Genotypes for Sustainable Food Security - Hafiz Ghulam Muhu-Din Ahmed; Yawen Zeng; Xiaomeng Yang; Anns Faisal; Noor Fatima; Aziz Ullah; Ghulam Sabir Hussain; Muhammad Iftikhar; Muhammad Rizwan Anwar (Journal of Crop Health, 2024)

Effect of multi-strain probiotics on the growth, hematological profile, blood biochemistry, antioxidant capacity, and physiological responses of Clarias batrachus fingerlings - Ayesha Tanveer; Noor Khan; Mahroze Fatima; Wazir Ali; Sadia Nazir; Sheeza Bano; Muhammad Asghar (Aquaculture International, 2024)

The heterogeneous impact of geopolitical risk and environment-related innovations on greenhouse gas emissions: The role of nuclear and renewable energy in the circular economy - Syed Tauseef Hassan; Danish; Muhammad Awais Baloch; Quocviet Bui; Noor Hashim Khan (Gondwana Research, 2024)

Exploring the role of social capital in flood risk reduction: Insights from a systematic review - Hassam Bin Waseem; Muhammad Noor E Elahi Mirza; Irfan Ahmad Rana (Environmental Impact Assessment Review, 2024)

Advanced network pharmacology and molecular docking-based mechanism study to explore the multi-target pharmacological mechanism of Cymbopogon citratus against Alzheimer's disease - Kinza Fatima; Usman Ali Ashfaq; Muhammad Tahir ul Qamar; Muhammad Asif; Asma Haque; Muhammad Qasim; Mubarak A. Alamri; Ziyad Tariq Muhseen; Fatima Noor; Muhammad Sadaqat (South African Journal of Botany, 2024)

In silico characterization of GbPAL, GbCHS, GbDFR and GbANS structural genes involved in the biosynthesis of flavonoids in Gynura bicolor DC - Nurul Jadid; Muhammad Rifqi Nur Ramadani; Aulia Febrianti Widodo; Noor Nailis Sa'adah; Dini Ermavitalini; Maulidia Rahmawati; Septi Anita Sari; Iro Datus Soleha; Faisol Mas'ud (South African Journal of Botany, 2024)

Co-application of biochar and plant growth regulators improves maize growth and decreases Cd accumulation in cadmium-contaminated soil - Fasih Ullah Haider; Noor-ul- Ain; Imran Khan; Muhammad Farooq; Habiba; Liqun Cai; Yuelin Li (Journal of Cleaner Production, 2024)

Functionalized carbon 1D/2D nanomaterials for effective water desalination: Synthesis, applications and cost issues. An overview - Umar Noor; Muhammad Fayyaz Farid; Ammara Sharif; Amna Saleem; Zubair Nabi; Muhammad Furqan Mughal; Kiran Abbas; Toheed Ahmed (Desalination, 2024)

Antibacterial effects of quercetagetin are significantly enhanced upon conjugation with chitosan engineered copper oxide nanoparticles - Adeelah Alvi; Saif Alqassim; Naveed Ahmed Khan; Bushra Khatoon; Noor Akbar; Muhammad Kawish; Shaheen Faizi; Muhammad Raza Shah; Ahmad M. Alharbi; Hasan Alfahemi; Ruqaiyyah Siddiqui (BioMetals, 2024)

Meta‐analysis contrasting freshwater biodiversity in forests and oil palm plantations with and without riparian buffers - Oscar Alberto Rojas‐Castillo; Sebastian Kepfer Rojas; Leandro Juen; Luciano Fogaça de Assis Montag; Fernando Geraldo Carvalho; Thiago Pereira Mendes; Kenny Wei Jie Chua; Clare L. Wilkinson; Mohammad Noor Azmai Amal; Muhammad Fahmi‐Ahmad; Dean Jacobsen (Conservation Biology, 2024)
The expansion of oil palm plantations has led to land‐use change and deforestation in the tropics, which has affected biodiversity. Although the impacts of the crop on terrestrial biodiversity have been extensively reviewed, its effects on freshwater biodiversity remain relatively unexplored. We reviewed the research assessing the impacts of forest‐to‐oil palm conversion on freshwater biota and the mitigating effect of riparian buffers on these impacts. We searched for studies comparing taxa richness, species abundance, and community composition of macroinvertebrates, amphibians, and fish in streams in forests (primary and disturbed) and oil palm plantations with and without riparian buffers. Then, we conducted a meta‐analysis to quantify the overall effect of the land‐use change on the 3 taxonomic groups. Twenty‐nine studies fulfilled the inclusion criteria. On average, plantations lacking buffers hosted 44% and 19% fewer stream taxa than primary and disturbed forests, respectively. Stream taxa on plantations with buffers were 24% lower than in primary forest and did not differ significantly from disturbed forest. In contrast, stream community composition differed between forests and plantations regardless of the presence of riparian buffers. These differences were attributed to agrochemical use and altered environmental conditions in the plantations, including temperature changes, worsened water conditions, microhabitat loss, and food and shelter depletion. On aggregate, abundance did not differ significantly among land uses because increases in generalist species offset the population decline of vulnerable forest specialists in the plantation. Our results reveal significant impacts of forest‐to‐oil palm conversion on freshwater biota, particularly taxa richness and composition (but not aggregate abundance). Although preserving riparian buffers in the plantations can mitigate the loss of various aquatic species, it cannot conserve primary forest communities. Therefore, safeguarding primary forests from the oil palm expansion is crucial, and further research is needed to address riparian buffers as a promising mitigation strategy in agricultural areas.

Synthesis of N-doped TiO2 nanoparticles with enhanced photocatalytic activity for 2,4-dichlorophenol degradation and H2 production - Javed Ali Khan; Murtaza Sayed; Noor S. Shah; Sanaullah Khan; Ashfaq Ahmad Khan; Muhammad Sultan; Ammar M. Tighezza; Jibran Iqbal; Grzegorz Boczkaj (Journal of Environmental Chemical Engineering, 2023)

Valorization of Momordica charantia seeds into phytogenically synthesized silver nanoparticles for the protection of oyster mushrooms against Trichoderma pleuroticola - Norhidayah Abd Aziz; Noor Hasyierah Mohd Salleh; Subash Chandra Bose Gopinath; Azlina Harun Kamaruddin; Muhammad Izzat Ridzuan; Nurul Afiqah Ahmad (Journal of Environmental Chemical Engineering, 2023)

Potential of milk fat globule membrane's phospholipids and anhydrous milk fat based nanostructured lipid carriers for enhanced bioaccessibility of vitamin D3 - Bina Zarif; Muhammad Haris; Ramla Shahid; Tauqir A. Sherazi; Abdur Rahman; Tayyaba Noor; Muhammad Imran (International Dairy Journal, 2023)

Proteosomes based on milk phospholipids and proteins to enhance the stability and bioaccessibility of β-carotene - Bina Zarif; Saima Shabbir; Ramla Shahid; Tayyaba Noor; Muhammad Imran (Food Chemistry, 2023)

Enhancing coastal ecosystem resilience: Investigating the interplay between safety criteria and ferry employee's perceptions to address climate change impacts - Muhammad Azizol Azmi; Kasypi Mokhtar; Noor Apandi Osnin; Suzanna Razali Chan; Gadah Albasher; Atif Ali; Alam Nawaz; Olakunle Oloruntobi; Lai Fatt Chuah (Environmental Research, 2023)

Different Rotation and Double Straw Returning Significantly Increase Liable Organic Carbon Content and Yield of Double Cropping Paddy Field in Southern China - Zhiqiang Wang; Haiying Tang; Guoqin Huang; Jianqun Miao; Ying Liu; Adnan Noor Shah; Muhammad Nawaz; Muhammad Ahsin Ayub; Muhammad Umair Hassan (International Journal of Plant Production, 2023)

Chromium removal from aqueous solution using bimetallic Bi0/Cu0-based nanocomposite biochar - Behzad Murtaza; Aqsa Naseer; Muhammad Imran; Noor S. Shah; Abdullah A. Al-Kahtani; Zeid A. ALOthman; Muhammad Shahid; Jibran Iqbal; Ghulam Abbas; Natasha Natasha; Muhammad Amjad (Environmental Geochemistry and Health, 2023)

Comparison of As removal efficiency and health risks from aqueous solution using as-synthesized Fe0 and Cu0: modelling, kinetics and reusability - Behzad Murtaza; Asad Ali; Muhammad Imran; Abdullah A. Al-Kahtani; Zeid A. ALOthman; Natasha Natasha; Muhammad Shahid; Noor S. Shah; Muhammad Asif Naeem; Sajjad Ahmad; Ghulam Murtaza (Environmental Geochemistry and Health, 2023)

Systematic elucidation of the multi-target pharmacological mechanism of Terminalia arjuna against congestive cardiac failure via network pharmacology and molecular modelling approaches - Aqsa Asghar; Muhammad Qasim; Fatima Noor; Usman Ali Ashfaq; Muhammad Tahir ul Qamar; Muhammad Shareef Masoud; Rashid Bhatti; Ahmad Almatroudi; Faris Alrumaihi; Khaled S. Allemailem (Natural Product Research, 2023)

Graphene-grafted bimetallic MOF membranes for hazardous & toxic contaminants treatment - Ayesha Rehman; Zaib Jahan; Muhammad Bilal Khan Niazi; Tayyaba Noor; Farhan Javed; Sarah I. Othman; Mostafa R. Abukhadra; Alam Nawaz (Chemosphere, 2023)

Selective capture of uranium and zirconium from strong HNO3 solution by ethenylphosphonic acid copolymerized polymer - Muhammad Hammad ul Haq; Xu Zhang; Fengqi Zhang; Alemtsehay Tesfay Reda; Dongxiang Zhang; Muhammad Zahid; Muhammad Khurram Tufail; Muhire Constantin; Noor Hasaan; Jinying Li; Xiyan Xu (Chemical Engineering Journal, 2023)

Antioxidant and antimicrobial activities of essential oils extracted from bamboo (Bambusa vulgaris) leaves and its application in skincare products: A review - Abu Hurairah Darwisy Alias; Nur Qistina Abdul Razak; Muhammad Hasnun Md Yusoff; Kian-Hui Chin; Mohd Lias Kamal; Noor Hafizah Uyup; Shafinas Abdullah; Nur Syuhada Ridzuan; Mardiana Saaid; Muhammad Hakimin Shafie (Biocatalysis and Agricultural Biotechnology, 2023)

Elucidating growth and biochemical characteristics of rice seedlings under stress from chromium VI salt and nanoparticles - Maryam Noor; Arif Ullah; Muhammad Israr Khan; Irum Raza; Muhammad Iqbal; Abdul Aziz; Gil Won Kim; Nadia Taimur; Azizullah Azizullah; Imran Ali; Pil Joo Kim (Environmental Science and Pollution Research, 2023)

Green synthesis and characterization of silver and copper nanoparticles and their use as an effective adsorbent for chromium removal and recovery from wastewater - Muhammad Atif Irshad; Sana Sattar; Arwa Abdulkreem AL-Huqail; Suliman M. S. Alghanem; Rab Nawaz; Noor ul Ain; Khalid Mahmud Hussaini; Amany H. A. Abeed (Environmental Science and Pollution Research, 2023)

Effect of green synthesized cerium oxide nanoparticles on fungal disease of wheat plants: A field study - Modhi O. Alotaibi; Nahaa M. Alotaibi; Adel M. Ghoneim; Noor ul Ain; Muhammad Atif Irshad; Rab Nawaz; Tahir Abbas; Amjad Abbas; Muhammad Rizwan; Shafaqat Ali (Chemosphere, 2023)

Heavy metals in five commonly consumed fish species from River Swat, Pakistan, and their implications for human health using multiple risk assessment approaches - Kifayatullah Khan; Maria Zeb; Muhammad Younas; Hafiz Muhammad Adeel Sharif; Muhammad Yaseen; Abdullah G. Al-Sehemi; Yasar N. Kavil; Noor Samad Shah; Xianghui Cao; Afsheen Maryam; Muhammad Qasim (Marine Pollution Bulletin, 2023)

Biogas Energy Resources in Pakistan Status, Potential, and Barriers - Muhammad Wakeel; Tasawer Hayat; Noor Samad Shah; Jibran Iqbal; Zia Ul Haq Khan; Ghulam Mustafa Shah; Atta Rasool (Utilities Policy, 2023)

Tailoring triple charge (O2−/H+/e−) conducting nature of Fe-based lanthanum doped samarium oxides for ceramic fuel cells (CFCs) - Muhammad Yousaf; Yuzheng Lu; Majid Niaz Akhtar; Ali Sarosh Khawaja; Khalid Mujasam Batoo; Sajjad Hussain; Asma Noor; Muhammad Akbar; Hu Enyi; M.A.K Yousaf Shah; Naveed Mushtaq; Bin Zhu (Fuel, 2023)

Variants in FREM1 and trisomy 18 identified in a neonatal progeria patient - Saima Siddiqi; Noor ul Ain; Mehran Kauser; Zahra Mukhtar; Muhammad Ansar; Muhammad Umair (Molecular Biology Reports, 2023)

Spatio-temporal analysis of river channel pattern in lower course of River Ravi using GIS and remote sensing - Noor-ul Huda; Shakeel Mahmood; Rida Sajjid; Muhammad Irfan Ahamad (Applied Geomatics, 2023)

Milk phospholipids and buttermilk based composite nanosystems for enhanced stability and bioaccessibility of β-carotene - Bina Zarif; Saima Shabbir; Abdur Rahman; Tauqir A. Sherazi; Ramla Shahid; Tayyaba Noor; Muhammad Imran (International Dairy Journal, 2023)

Titanium oxide/nickel foam (TiO2/NF) catalyzed the conversion of glucose to 5-hydroxymethylfurfural in subcritical solvothermal liquefaction - Muhammad Amirul Aiman Bin Abdul Rani; Nabila A. Karim; Noor Shahirah Shamsul; Siti Kartom Kamarudin (Fuel, 2023)

Efficacy of γ-Aminobutyric Acid (GABA) on Physio-biochemical Attributes of Lettuce (Lactuca sativa L.) Under Cadmium Toxicity - Zainab Waris; Zahra Noreen; Anis Ali Shah; Sheeraz Usman; Adnan Noor Shah; Muhammad Rizwan; Ryan Casini; Hosam O. Elansary (Journal of Plant Growth Regulation, 2023)

Trehalose: A Key Player in Plant Growth Regulation and Tolerance to Abiotic Stresses - Muhammad Umair Hassan; Muhammad Nawaz; Adnan Noor Shah; Ali Raza; Lorenzo Barbanti; Milan Skalicky; Mohamed Hashem; Marian Brestic; Saurabh Pandey; Saad Alamri; Yasser S. Mostafa; Ayman E. L. Sabagh; et al. (Journal of Plant Growth Regulation, 2023)

Applied pedagogies for higher education: Real-world learning and innovation across the curriculum - Muhammad Younas; Samina Khalid; Uzma Noor (The Social Science Journal, 2023)

Lauric acid improves hormonal profiles, antioxidant properties, sperm quality and histomorphometric changes in testis and epididymis of streptozotocin-induced diabetic infertility rats - Nursarah Syamimi Anuar; Syahirah Ain Shafie; Muhammad Aiman Faris Maznan; Noor Syaffinaz Noor Mohamad Zin; Nur Ain Sabrina Azmi; Rohaizad Abdul Raoof; Diyas Myrzakozha; Nurdiana Samsulrizal (Toxicology and Applied Pharmacology, 2023)

Impact of alternate Mn doping in ternary nanocomposites on their structural, optical and antimicrobial properties: Comparative analysis of photocatalytic degradation and antibacterial activity - Noor Tahir; Muhammad Zahid; Asim Jillani; Suman Tahir; Muhammad Yaseen; Qamar Abbas; Rana Abdul Shakoor; Syed Zajif Hussain; Imran Shahid (Journal of Environmental Management, 2023)

Knowledge mapping of cool pavement technologies for urban heat island Mitigation: A Systematic bibliometric analysis - Taqia Rahman; Muhammad Zudhy Irawan; Anissa Noor Tajudin; M. Rizka Fahmi Amrozi; Iswandaru Widyatmoko (Energy and Buildings, 2023)

Heavy Metal Occurrence, Pathways, and Associated Socio-ecological Risks in Riverine Water: Application of Geographic Information System, Multivariate Statistics, and Risk Assessment Models - Kifayatullah Khan; Muhammad Younas; Muhammad Sajawal Khan; Xu Li; Muhammad Fawad; Noor Samad Shah; Jafar Ali; Sana Ullah; Muhammad Ayaz; Afsheen Maryam; Asmat Ali; Akhtar Zeb Khan; et al. (Water, Air, & Soil Pollution, 2023)

Development of high-capacity surface-engineered MXene composite for heavy metal Cr (VI) removal from industrial wastewater - Umair Ali Asif; Khalid Mahmood; Salman Raza Naqvi; Muhammad Taqi Mehran; Tayyaba Noor (Chemosphere, 2023)

Application of GABA (γ-aminobutyric acid) to improve saline stress tolerance of chufa (Cyperus esculentus L. var. sativus Boeck) plants by regulating their antioxidant potential and nitrogen assimilation - Abd Ullah; Akash Tariq; Fanjiang Zeng; Javaria Noor; Jordi Sardans; Muhammad Ahsan Asghar; Zhihao Zhang; Josep Peñuelas (South African Journal of Botany, 2023)

Potential of pectin-chitosan based composite films embedded with quercetin-loaded nanofillers to control meat associated spoilage bacteria - Syed Muhammad Afroz Ali; Taskeen Niaz; Anas Munir; Ramla Shahid; Saima Shabbir; Tayyaba Noor; Muhammad Imran (Food Bioscience, 2023)

Petiole micromorphology in Brassicaceous taxa and its potential for accurate taxonomic identification - Wajia Noor; Muhammad Zafar; Mushtaq Ahmad; Ashwaq T. Althobaiti; Mohamed Fawzy Ramadan; Trobjon Makhkamov; Yusufjon Gafforov; Akramjon Yuldashev; Oybek Mamarakhimov; Omer Kilic; Heba F. Eid; Talip Şahin; et al. (Flora, 2023)

Potassium-Nitrogen Ratio Improved Cotton Yield by Regulating Antioxidant Metabolism Under a New Cropping Model for the Yangtze River Valley of China - Saif Ali; Abdul Hafeez; Xiaolei Ma; Shahbaz Atta Tung; Muhammad Sohaib Chattha; Shoaib Ahmad; Adnan Noor Shah; Guozheng Yang (Journal of Soil Science and Plant Nutrition, 2023)

Effects of Winter Cropping on rice Yield, Economic Benefit, and Resource Utilization Efficiency on Different Cropping Systems of Paddy Field in the Middle Reaches of the Yangtze River - Haiying Tang; Guiyuan Meng; Wenjie Jiang; Ying Liu; Athar Mahmood; Adnan Noor Shah; Muhammad Nawaz; Muhammad Umair Hassan; Guoqin Huang (International Journal of Plant Production, 2023)

Cassia absus-mediated upregulation of IL-4, IL-10 and downregulation of IL-1β, IL-6, TNF- α, NF-κB, IFN-γ in CFA-induced arthritis model - Bazgha Gul; Rukhsana Anwar; Mohammad Saleem; Afifa Noor; Muhammad Ihsan Ullah (Inflammopharmacology, 2023)

Synergism: biocontrol agents and biostimulants in reducing abiotic and biotic stresses in crop - Muhammad Salahudin Kheirel Anuar; Amalia Mohd Hashim; Chai Ling Ho; Mui-Yun Wong; Shamala Sundram; Noor Baity Saidi; Mohd Termizi Yusof (World Journal of Microbiology and Biotechnology, 2023)

Genetic analysis of ACE2 peptidase domain in SARS-CoV-2-positive and SARS-CoV-2-negative individuals from Pakistan - Noor Muhammad; Humaira Naeemi; Ayesha Azeem; Rida Sadaqat; Umara Shehzad; Kashif Siddique; Usman Hassan; Aun Raza; Muhammad Usman Rashid (Molecular Biology Reports, 2023)

Bioremediation of heavy metals polluted environment and decolourization of black liquor using microbial biofilms - Iram Liaqat; Noor Muhammad; Chaman Ara; Uzma Hanif; Saiqa Andleeb; Muhammad Arshad; Muhammad Nauman Aftab; Chand Raza; Muhammad Mubin (Molecular Biology Reports, 2023)

Combined Effect of Rice-Straw Biochar and Humic Acid on Growth, Antioxidative Capacity, and Ion Uptake in Maize (Zea mays L.) Grown Under Saline Soil Conditions - Zaffar Malik; Natasha Malik; Iqra Noor; Muhammad Kamran; Aasma Parveen; Muhammad Ali; Freeha Sabir; Hosam O. Elansary; Tarek K. Zin El-Abedin; Eman A. Mahmoud; Shah Fahad (Journal of Plant Growth Regulation, 2023)

A critical analysis of sources, pollution, and remediation of selenium, an emerging contaminant - Habib Ullah; Lu Lun; Audil Rashid; Noor Zada; Baoliang Chen; Asfandyar Shahab; Ping Li; Muhammad Ubaid Ali; Siyi Lin; Ming Hung Wong (Environmental Geochemistry and Health, 2023)

Language teacher agency - Muhammad Younas; Uzma Noor; Samina Khalid (The Social Science Journal, 2023)

Advances in production & activation of marine macroalgae-derived biochar catalyst for sustainable biodiesel production - Muhammad Zubair Yameen; Hamad AlMohamadi; Salman Raza Naqvi; Tayyaba Noor; Wei-Hsin Chen; Nor Aishah Saidina Amin (Fuel, 2023)

Wild food plants gathered by four cultural groups in North Waziristan, Pakistan - Noor Khalid; Lal Badshah; Adnan Ali Shah; Arman Ullah; Naushad Khan; Muhammad Abdul Aziz; Renata Sõukand; Andrea Pieroni (Genetic Resources and Crop Evolution, 2023)

Triticum aestivum: antioxidant gene profiling and morpho-physiological studies under salt stress - Musarrat Ramzan; Memoona Gillani; Anis Ali Shah; Adnan Noor Shah; Naheed Kauser; Muhammad Jamil; Rana Touqeer Ahmad; Sami Ullah (Molecular Biology Reports, 2023)

Synthesis and characterization of porous reduced graphene oxide based geopolymeric membrane with titanium dioxide coating for forward osmosis application - Kashif Khan; Muhammad Irfan; Noor Ul Amin; Heqing Jiang; Saeed Gul (Chemosphere, 2023)

Recent progress in catalytic deoxygenation of biomass pyrolysis oil using microporous zeolites for green fuels production - Salman Raza Naqvi; Asif Hussain Khoja; Imtiaz Ali; Muhammad Naqvi; Tayyaba Noor; Awais Ahmad; Rafael Luque; Nor Aishah Saidina Amin (Fuel, 2023)

Characterisation and selection of freshwater cyanobacteria for phycobiliprotein contents - Hui Teng Tan; Fatimah Md. Yusoff; Yam Sim Khaw; Muhammad Farhan Nazarudin; Nur Amirah Izyan Noor Mazli; Siti Aqlima Ahmad; Noor Azmi Shaharuddin; Tatsuki Toda (Aquaculture International, 2023)

The mechanism for bond behavior of concrete with two-staged treated rubber filled steel tube - Abu Bakar Nabilah; Nor Azizi Safiee; Noor Azline Mohd Nasir; Muhammad Fakhrul Radzi Abdul Rahman; Abdulrahman Khaleel Midhin (European Journal of Environmental and Civil Engineering, 2023)

Analysis of Temperature Data Using the Innovative Trend Pivot Analysis Method and Trend Polygon Star Concept: A Case Study of Soan River Basin, Potohar, Pakistan - Fiaz Hussain; Ray-Shyan Wu; Ghulam Nabi; Rana Shahzad Noor; Muhammad Naveed Anjum; Muhammad Azam; Arslan Afzal (Pure and Applied Geophysics, 2023)
The trend analysis approach is used to estimate changing climate and its impact on the environment, agriculture and water resources. Innovative polygonal trend analyses are qualitative methods applied to detect changes in the environment. In this study, the Innovative Trend Pivot Analysis Method (ITPAM) and Trend Polygon Star Concept Method were applied for temperature trend detection in Soan River Basin (SRB), Potohar region, Pakistan. The average monthly temperature data (1995–2020) for 11 stations were used to create polygon graphics. Trend length and slope were calculated separately for arithmetic mean and standard deviation. The innovative methods produced useful scientific information, with the identification of monthly shifts and trend behaviors of temperature data at different stations. Some stations showed an increasing trend and others showed decreasing behavior. This increasing and decreasing variability is the result of climate change. The winter season temperature is increasing, and the months of December to February are getting warmer. Summer is expanding and pushing autumn towards winter, swallowing the early period of the cold season. The monthly polygonal trends with risk graphs depicted a clear picture of climate change in the Potohar region of Pakistan. The phenomena of observed average temperature changes, indicated by both qualitative methods, are interesting and have the potential to aid water managers’ understanding of the cropping system of the Potohar region.

Chemopreventive role of probiotics against cancer: a comprehensive mechanistic review - Shehzeen Noor; Shaukat Ali; Shumaila Riaz; Iqra Sardar; Muhammad Adeel Farooq; Ayesha Sajjad (Molecular Biology Reports, 2023)

Prevalence of FANCM germline variants in BRCA1/2 negative breast and/or ovarian cancer patients from Pakistan - Muhammad Usman Rashid; Noor Muhammad; Umara Shehzad; Faiz Ali Khan; Asif Loya; Ute Hamann (Familial Cancer, 2023)

Trehalose: a promising osmo-protectant against salinity stress—physiological and molecular mechanisms and future prospective - Muhammad Nawaz; Muhammad Umair Hassan; Muhammad Umer Chattha; Athar Mahmood; Adnan Noor Shah; Mohamed Hashem; Saad Alamri; Maria Batool; Adnan Rasheed; Maryam A. Thabit; Haifa A. S. Alhaithloul; Sameer H. Qari (Molecular Biology Reports, 2022)

Sedimentology and diagenesis control on reservoir quality of Sheikhan Limestone (Eocene) at the Panoba and Sheikhan Nala Section, Kohat Basin, Pakistan - Atif Salim; Muhammad Kashif; Bin Dou; Danish Khan; Muhammad Jawad Munawar; Noor Ahmed; Naveed Rehman; Muhammad Sajid; Zahid Ullah; Muhammad Tariq (Carbonates and Evaporites, 2022)

Capturing spatial variability of factors affecting the water allocation plans—a geo-informatics approach for large irrigation schemes - Muhammad Mohsin Waqas; Muhammad Waseem; Sikandar Ali; Jan W. Hopman; Usman Khalid Awan; Syed Hamid Hussain Shah; Adnan Noor Shah (Environmental Science and Pollution Research, 2022)

Genomic constitution and relationships of Ziziphus species collected from Malakand Division, Pakistan - Nisar Uddin; Noor Muhammad; Niaz Ali; Mohammad Nisar; Mengjun Liu (Physiology and Molecular Biology of Plants, 2022)

Exploring thiazole-linked thioureas using alkaline phosphatase assay, biochemical evaluation, computational analysis and structure–activity relationship (SAR) studies - Sajid Ali Channar; Pervaiz Ali Channar; Aamer Saeed; Aisha A. Alsfouk; Syeda Abida Ejaz; Rabail Ujan; Razia Noor; Muhammad Sajjad Bilal; Qamar Abbas; Zahid Hussain; Bilal Ahmad Khan; Hussain Raza; et al. (Medicinal Chemistry Research, 2022)

Linking Plants Functioning to Adaptive Responses Under Heat Stress Conditions: A Mechanistic Review - Mahmood Ul Hassan; Tassaduq Rasool; Chandni Iqbal; Adnan Arshad; Muhammad Abrar; Muhammad Mohsin Abrar; Muhammad Habib-ur-Rahman; Mehmood Ali Noor; Alam Sher; Shah Fahad (Journal of Plant Growth Regulation, 2022)

A time series forecasting analysis of overall and sector-based natural gas demand: a developing South Asian economy case - Anwar Hussain; Junaid Alam Memon; Muntasir Murshed; Md Shabbir Alam; Usman Mehmood; Mohammad Noor Alam; Muhammad Rahman; Umar Hayat (Environmental Science and Pollution Research, 2022)

Influence of temperature on the development and reproduction of Spodoptera litura (Fabricius) on castor bean: implications for its use as a trap crop - Muhammad Zakria; Muhammad Shah Zaib; Khalid Abbas; Muhammad Sarmad; Syed Muhammad Zaka; Muhammad Noor-ul-Ane (Arthropod-Plant Interactions, 2022)

Mapping of marine lobster research: A global outlook - Mohamad Nor Azra; Mok Wen Jye; Hien Van Doan; Ivar Zekker; Muhammad Fuad Abdullah; Zulkiflee Abd Latif; Mohd Iqbal Mohd Noor (Frontiers in Marine Science, 2022)
This study examined research and development of the commercially important marine lobster, in terms of descriptive metadata and scientometric analysis. We consider a collection of over 9,578 related articles to assess literature patterns and research development trends related to marine lobsters as a topic. Web of Science Core Collection was used to identify, collate, and generate publication trends, a list prominent authors and affiliations involved, countries that actively participated, and the co-citation analysis of the references as well as impactful articles and keywords. There were 149 different countries or states that had relevant publications on lobster research. We found an increase in the number of publications over time, with the USA having the most number of publications, followed by Australia and Canada. A total of 17,782 authors were involved in the field of lobster studies. Canadian researchers had the highest citation count for marine lobster research. Surprisingly, the most impactful keyword was crayfish, followed by neuron and amino acid sequence. Our study identifies the multidisciplinary nature in marine lobster research, which includes fields such as neuroscience and developmental genetics. We find that lobster scientific publications increasingly center on the broader coverage areas of science such as taxonomy and basic biology.

Evaluating dual exposure by using climate-conflict vulnerability index on the coastal districts of Sindh, Pakistan - Noor Fatima; Aamir Alamgir; Moazzam Ali Khan; Muhammad Owais (Environmental Monitoring and Assessment, 2022)

Occurrence of Microplastics and Heavy Metals in Aquatic and Agroecosystem: A Case Study - Tanveer Ahmad; Muhammad Amjad; Qumer Iqbal; Asmat Batool; Anam Noor; Muhammad Jafir; Hammad Hussain; Muhammad Irfan (Bulletin of Environmental Contamination and Toxicology, 2022)

Assessment of Malaysian brown seaweed Padina gymnospora antioxidant properties and antimicrobial activity in different solvent extractions - Muhammad Farhan Nazarudin; Muhammad Syazwan Shahidan; Nur Amirah Izyan Noor Mazli; Tan Hui Teng; Yam Sim Khaw; Ina Salwany Md Yasin; Azizul Isha; Mohammed Aliyu-Paiko (Fisheries Science, 2022)

Hydrogen peroxide priming alleviates salinity induced toxic effect in maize by improving antioxidant defense system, ionic homeostasis, photosynthetic efficiency and hormonal crosstalk - Muhammad Umer Chattha; Muhammad Uzair Ul Hassan; Imran Khan; Muhammad Nawaz; Adnan Noor Shah; Abdul Sattar; Mohamed Hashem; Saad Alamri; Muhammad Talha Aslam; Haifa A. S. Alhaithloul; Muhammad Umair Hassan; Sameer H. Qari (Molecular Biology Reports, 2022)

CRISPR/Cas9 is a powerful tool for precise genome editing of legume crops: a review - Adnan Rasheed; Aminah A. Barqawi; Athar Mahmood; Muhammad Nawaz; Adnan Noor Shah; Daniyah H. Bay; Maryam A. Alahdal; Muhammad Umair Hassan; Sameer H. Qari (Molecular Biology Reports, 2022)

MiRNA fine tuning for crop improvement: using advance computational models and biotechnological tools - Asad Abbas; Adnan Noor Shah; Mohsin Tanveer; Waseem Ahmed; Anis Ali Shah; Sajid Fiaz; Muhammad Mohsin Waqas; Sami Ullah (Molecular Biology Reports, 2022)

Recent trends in microalgal harvesting: an overview - Natasha Laraib; Ali Hussain; Arshad Javid; Tahir Noor; Qurat-ul-Ain Ahmad; Asma Chaudhary; Maleeha Manzoor; Muhammad Akmal; Syed Mohsin Bukhari; Waqas Ali; Tae Jin Choi; Peer M. Schenk (Environment, Development and Sustainability, 2022)

Characterisation of graphene oxide-coated sand for potential use as proppant in hydraulic fracturing - Ainni Syuhada Ramlan; Rohani Mohd Zin; Noor Fitrah Abu Bakar; Nur Hidayati Othman; Husna Hayati Jarni; Mohamed Hasaan Hussain; Nabil Imran Mohd Najib; Muhammad Zulhasbullah Zakran (Arabian Journal of Geosciences, 2022)

A modified approach to quantify aquifer vulnerability to pollution towards sustainable groundwater management in Irrigated Indus Basin - Muhammad Umar; Shahbaz Nasir Khan; Arfan Arshad; Rana Ammar Aslam; Hafiz Muhammad Safdar Khan; Haroon Rashid; Quoc Bao Pham; Abdul Nasir; Rabeea Noor; Khaled Mohamed Khedher; Duong Tran Anh (Environmental Science and Pollution Research, 2022)

Functionalized multi-walled carbon nanotubes for oil spill cleanup from water - Thamer Adnan Abdullah; Tatjana Juzsakova; Sanaa A. Hafad; Rashed Taleb Rasheed; Noor Al-Jammal; Muhammad Ali Mallah; Ali Dawood Salman; P. C. Le; Endre Domokos; Mustafa Aldulaimi (Clean Technologies and Environmental Policy, 2022)
The growing global economy resulted in an incessant increase in transportation and exploitation of oil. Hence, the oil spillage has been considered a serious threat to aquatic and terrestrial ecosystems. Therefore, water purification has been considered a major challenge around the world. There are numerous classical methods available for oil removal from water, but owing to multiple defects and disadvantages, research efforts have focused to find such adsorbents which can improve oil adsorption capability. Traditional adsorbent material typically applied in oil removal includes activated carbon, organoclays, wool, zeolites, etc. These materials suffer from several drawbacks such as low absorption capacity, non-selective absorption, and complicated reusability, whereas nano-adsorbents offer multiple advantages such as having multiple sorption sites, large surface area, short intra-particle diffusion distance, tuneable pore size, and ease of low-temperature modification. Multi-walled carbon nanotubes (MWCNTs) are extensively used adsorbent materials with a strong affinity for the removal of organic pollutants. The functionalization MWCNTs further increase the sorption capacity of adsorbents manifolds to remove organic materials. These nanocomposites are also compatible with green materials and considered environmentally friendly adsorbents. This review paper aims at providing an insight to understand the properties of the MWCNTs and their potential use to adsorb hydrocarbons from water. Moreover, the synthesis methods of those materials, their modification procedures including the functionalization with metal oxide nanoparticles, and applications are also discussed in detail. Graphic abstract

Bacterial prediction using internet of things (IoT) and machine learning - Hamza Khurshid; Rafia Mumtaz; Noor Alvi; Ayesha Haque; Sadaf Mumtaz; Faisal Shafait; Sheraz Ahmed; Muhammad Imran Malik; Andreas Dengel (Environmental Monitoring and Assessment, 2022)

Wind exposure and sediment type determine the resilience and response of seagrass meadows to climate change - Jaco C. de Smit; Muhammad S. Bin Mohd Noor; Eduardo Infantes; Tjeerd J. Bouma (Limnology and Oceanography, 2022)
Seagrasses and bare sediment represent alternative stable states, with sediment resuspension being a key driver of system stability via the Seagrass–Sediment–Light (SSL) feedback. We explore the SSL feedback by quantifying the sediment stabilization by seagrass, and using these measurements to calculate under which conditions seagrass ends up in a turbid environment. We quantified in‐situ sediment resuspension velocity thresholds ( u cr ) for Zostera marina growing in medium to fine sand, using a field flume inducing near‐bed wave motion. u cr was determined for full length shoots, shoots clipped to 0.08 m, and removed shoots. We found that rhizomes did not influence u cr of the top sediment layer. Overall, u cr was linearly related to blade area, which became independent for sediment type when normalizing u cr for the resuspension threshold after shoot removal. Comparing measured u cr against natural wave conditions showed that the seagrass meadow at the study site is currently stable. Exploring the effects of changing hydrodynamic conditions revealed that effects of increasing storminess has limited influence on sediment resuspension and thus the SSL‐feedback. Increasing mean wind velocity had a stronger influence on SSL‐feedback dynamics by causing more frequent exceedance of u cr . The response of seagrasses to increasing wind pressure depends on bay topography. A fully exposed Z. marina meadow under low initial turbidity pressure trended toward bistability, as turbidity pressure increased mainly on bare sediments. The study site and a fully exposed Z. marina meadow under high initial turbidity pressure saw an increase in turbidity across all blade areas.

Cellulosic fiber nanocomposite application review with zinc oxide antimicrobial agent nanoparticle: an opt for COVID-19 purpose - Amizon Azizan; Aisyah Afiqah Samsudin; Minhalina Batrisyia Shamshul Baharin; Muhammad Harith Dzulkiflee; Nor Roslina Rosli; Noor Fitrah Abu Bakar; Muhammad Adlim (Environmental Science and Pollution Research, 2022)

Nitrification Inhibitor and Plant Growth Regulators Improve Wheat Yield and Nitrogen Use Efficiency - Khadim Dawar; Umar Rahman; Syed Sartaj Alam; Mohammad Tariq; Aamir Khan; Shah Fahad; Rahul Datta; Subhan Danish; Shah Saud; Muhammad Noor (Journal of Plant Growth Regulation, 2022)

Fabrication of visible light active Mn-doped Bi2WO6-GO/MoS2 heterostructure for enhanced photocatalytic degradation of methylene blue - Noor Tahir; Muhammad Zahid; Ijaz Ahmad Bhatti; Yasir Jamil (Environmental Science and Pollution Research, 2022)

Response of root development and nutrient uptake of two chinese cultivars of hybrid rice to nitrogen and phosphorus fertilization in Sichuan Province, China - Guotao Yang; Farhan Nabi; Sumbal Sajid; Abdul Rasheed Kaleri; Ali Murad Jakhar; Liang Cheng; Martin Raspor; Noor Muhammad; Jun Ma; Yungao Hu (Molecular Biology Reports, 2021)
Background Chemical fertilization helped modern agriculture in grain yield improvement to ensure food security. The response of chemical fertilization for higher hybrid rice production is highly dependent on optimal fertilization management in paddy fields. To assess such responses, in the current work we examine the yield, root growth, and expression of related genes responsible for stress metabolism of nitrogen (N) and phosphorus (P) in two hybrid-rice cultivars Deyou4727 (D47) and Yixiangyou2115 (Y21). Methods and results The experiment followed four nitrogen (N) (N 0 , N 60 , N 120, and N 180 kg/ha) and phosphorus (P) (P 0 , P 60 , P 90 , and P 120 kg/ha) fertilizer levels. The grain yield in D47 was more sensitive to nitrogen application, while Y21 was more sensitive to phosphorus application, which resulted in comparatively higher biomass and yield. Our findings were corroborated by gene expression studies of glutamine synthetase OsGS1;1 and OsGS1;2 and phosphate starvation-related genes PHR1 and SPX , confirming sensitivity to N and P application. The number of roots was less sensitive to nitrogen application in D47 between N 0 and N 60 , but the overall nutrient response difference was significantly higher due to the deep rooting system as compared to Y21. Conclusions The higher yield, high N and P use efficiency, and versatile root growth of D47 make it suitable to reduce unproductive usage of N and P from paddy fields, improving hybrid rice productivity, and environmental safety in the Sichuan basin area of China.

Publisher Correction: Liquisolid Technique: a Novel Tool to Develop Aceclofenac-Loaded Eudragit L-100 and RS-100-Based Sustained Release Tablets - Yaseen Hussain; Asim.ur. Rehman; Muhammad Noor Shah (Journal of Pharmaceutical Innovation, 2021)

Liquisolid Technique: a Novel Tool to Develop Aceclofenac-Loaded Eudragit L-100 and RS-100-Based Sustained Release Tablets - Yaseen Hussain; Asim.ur.Rehman; Muhammad Noor Shah (Journal of Pharmaceutical Innovation, 2021)

Carbon nanotubes from waste cooking palm oil as adsorbent materials for the adsorption of heavy metal ions - Suriani Abu Bakar; Norhafizah Jusoh; Azmi Mohamed; Muqoyyanah Muqoyyanah; Mohd Hafiz Dzarfan Othman; Mohamad Hafiz Mamat; Mohd Khairul Ahmad; Mohd Ambri Mohamed; Muhammad Noor Azlan; Norhayati Hashim; Muhammad Danang Birowosuto; Tetsuo Soga (Environmental Science and Pollution Research, 2021)

Screening of wheat (Triticum aestivum L.) genotypes for drought tolerance using polyethylene glycol - Muhammad Adnan Bukhari; Adnan Noor Shah; Shah Fahad; Javaid Iqbal; Fahim Nawaz; Abdul Manan; Mohammad Safdar Baloch (Arabian Journal of Geosciences, 2021)

Isolation of tyrosine derived phenolics and their possible beneficial role in anti-inflammatory and antioxidant potential of Tithonia tubaeformis - Noor Ul Ain Nawaz; Muhammad Saeed; Khalid Mohammed Khan; Irfan Ali; Huma Aslam Bhatti; Sabi-Ur-Rehman; Muhammad Shahid; Shaheen Faizi (Natural Product Research, 2021)

Essential oil composition and antibacterial activity of Canarium strictum Roxb. resin - Halima Tahir; Nadeem Muhammad; Azeem Intisar; Muhammad Imran Din; Uzma Qaisar; Muhammad Abdul Qadir; Noor Ul Ain; Zeeshan Ahmad; Pakeeza Aziz; Muhammad Khurram Shahzad; Irshad Hussain (Plant Biosystems, 2021)

Heavy Metals Accumulation in Dragonflies (Odonata) and Their Habitats in District Swabi, Khyber Pakhtunkhwa, Pakistan: Assessing Dragonfly Bionomics in the Region - Hajra Noor-Ul-Islam; Khurshaid Khan; Syed Ahmed Zia; Muhammad Naeem; Waqas Ahmad Shams (Bulletin of Environmental Contamination and Toxicology, 2021)

Effect of Hydrogen Peroxide on Plant Growth, Photosynthesis, Leaf Histology and Rubisco Gene Expression of the Ficus deltoidea Jack Var. deltoidea Jack - Nik Nurnaeimah Nik Muhammad Nasir; Mohammad Moneruzzaman Khandaker; Khamsah Suryati Mohd; Noor Afiza Badaluddin; Normaniza Osman; Nashriyah Mat (Journal of Plant Growth Regulation, 2021)

Striving towards environmental sustainability: how natural resources, human capital, financial development, and economic growth interact with ecological footprint in China - Sayma Zia; Mustaghis ur Rahman; Mohammed Hassan Noor; Muhammad Kamran Khan; Munaza Bibi; Danish Iqbal Godil; Muhammad Umer Quddoos; Muhammad Khalid Anser (Environmental Science and Pollution Research, 2021)

Physiopathology and effectiveness of therapeutic vaccines against human papillomavirus - Noor Ayesha; Sara Aboulaghras; Muhammad Jahangeer; Areej Riasat; Rehana Ramzan; Rameen Fatima; Muhammad Akram; Abdelaali Balahbib; Abdelhakim Bouyahya; Ekaterina Sepiashvili; Gokhan Zengin; Mohammad Ali Shariati (Environmental Science and Pollution Research, 2021)

Impact of globalization, foreign direct investment, and energy consumption on CO2 emissions in Bangladesh: Does institutional quality matter? - Md. Monirul Islam; Muhammad Kamran Khan; Mohammad Tareque; Noor Jehan; Vishal Dagar (Environmental Science and Pollution Research, 2021)

Traditional and cultural uses of medicinal plant species in the flora of Kuz Abakhel, for the treatment of various ailments - Noor Muhammad; Nisar Uddin; Muhammad Khalil Ullah Khan; Muhammad Umer; Niaz Ali; Shariat Ullah (Advances in Traditional Medicine, 2021)

SSR-based population structure, molecular diversity and identity cards of Ziziphus species from Pakistan and China - Nisar Uddin; Niaz Ali; Mohammad Nisar; Mengjun Liu; Zhiguo Liu; Noor Muhammad; Inayat Ur Rahman (Genetic Resources and Crop Evolution, 2021)

Distribution and health risk assessment of trace elements in ground/surface water of Kot Addu, Punjab, Pakistan: a multivariate analysis - Zafar Abbas; Muhammad Imran; Natasha Natasha; Behzad Murtaza; Muhammad Amjad; Noor Samad Shah; Zia Ul Haq Khan; Iftikhar Ahmad; Sajjad Ahmad (Environmental Monitoring and Assessment, 2021)

Geospatially mapping carbon stock for mountainous forest classes using InVEST model and Sentinel-2 data: a case of Bagrote valley in the Karakoram range - Muhammad Imran; Noor ud Din (Arabian Journal of Geosciences, 2021)

Optimization, in vitro release and toxicity evaluation of novel pH sensitive itaconic acid-g-poly(acrylamide)/sterculia gum semi-interpenetrating networks - Fauzia Rehman; Ikram Ullah Khan; Syed Haroon Khalid; Sajid Asghar; Muhammad Irfan; Ikrima Khalid; Akhtar Rasul; Huma Mahmood; Abid Mehmood Yousaf; Yasser Shahzad; Muhammad Mudassar; Noor Ul Amin Mohsin (DARU Journal of Pharmaceutical Sciences, 2021)

Dietary supplementations of methionine improve growth performances, innate immunity, digestive enzymes, and antioxidant activities of rohu (Labeo rohita) - Zohaib Noor; Mannal Noor; Syed Allauddin Khan; Waqar Younas; Daniya Ualiyeva; Zaigham Hassan; Ali Muhammad Yousafzai (Fish Physiology and Biochemistry, 2021)

Projected drought pattern under climate change scenario using multivariate analysis - Muhammad Waseem; Muhammad Ajmal; Ijaz Ahmad; Noor Muhammad Khan; Muhammad Azam; Muhammad Kaleem Sarwar (Arabian Journal of Geosciences, 2021)

Impact of Urbanization on Groundwater Levels in Rawalpindi City, Pakistan - Faraz ul Haq; Usman Ali Naeem; Hamza Farooq Gabriel; Noor Muhammad Khan; Ijaz Ahmad; Habib Ur Rehman; Muhammad Awais Zafar (Pure and Applied Geophysics, 2021)

Streamflow Variations in Monthly, Seasonal, Annual and Extreme Values Using Mann-Kendall, Spearmen’s Rho and Innovative Trend Analysis - Muhammad S. Ashraf; Ijaz Ahmad; Noor M. Khan; Fan Zhang; Ahmed Bilal; Jiali Guo (Water Resources Management, 2021)

Influence of Different Organic Manures and Their Combinations on Productivity and Quality of Bread Wheat - Nauman Ali; Muhammad Naeem Khan; Muhammad Saeed Ashraf; Sobia Ijaz; Hafiz Saeed-ur-Rehman; Muhammad Abdullah; Noor Ahmad; Hafiz Muhammad Akram; Muhammad Farooq (Journal of Soil Science and Plant Nutrition, 2020)

Enhancement of photocatalytic potential and recoverability of Fe3O4 nanoparticles by decorating over monoclinic zirconia - Idrees Khan; Noor Zada; Ibrahim Khan; Muhammad Sadiq; Khalid Saeed (Journal of Environmental Health Science and Engineering, 2020)

Assessing inflow variability at rim stations of the Indus Basin Irrigation System * - Yasir Abbas; Noor Muhammad Khan; Habib‐Ur‐Rehman Mughal; Khalid Mahmood (Irrigation and Drainage, 2020)
Having one of the largest interconnected irrigation systems in the world, the distribution of irrigation water in Pakistan is largely dependent on river supplies. Seasonal planning of water distribution in the country ignores day‐to‐day inflow variability which impacts water distribution operations. This study has been carried out to assess the inflow variability at four rim stations of the Indus Basin Irrigation System (IBIS) in Pakistan, namely: Kabul River at Noshera, Indus River at Tarbela, Jhelum River at Mangla, and Chenab River at Marala. Nine vital hydrological parameters, depicting various aspects of variability, were computed using 24 years of daily inflow time series. Analysis indicated that Mangla and Marala stations depicted more instances of high flow pulses, which highlighted their flashy nature compared to Noshera and Tarbela whose contributions were mainly from snowmelt. Mangla and Marala stations also depicted higher variations in terms of number and duration of low flow pulses, whereas least low flow variations were observed at Tarbela. Assessment of variability indicated that Tarbela exhibited minimum variations in inflows in the months of October to January, while Marala showed highest inflow variations among all stations in the same months. This study identified successfully the critical months of high flow variability, in addition to identification of the climate shift in the region—two aspects that need attention in future planning and operations.

Developing the first halophytic turfgrasses for the urban landscape from native Arabian desert grass - Muhammad Zamin; Shah Fahad; Abdul Mateen Khattak; Muhammad Adnan; Fazli Wahid; Ahmad Raza; Depeng Wang; Shah Saud; Muhammad Noor; Hafiz Faiq Bakhat; Muhammad Mubeen; Hafiz Mohkum Hammad; et al. (Environmental Science and Pollution Research, 2020)

Antibacterial and antioxidant activity of naphthofuranquinones from the twigs of tropical mangrove Avicennia officinalis - Suvik Assaw; Muhammad Isyraq Hazim Mohd Amir; Tyng Tyng Khaw; Kamariah Bakar; Siti Aisha Mohd Radzi; Noor Wini Mazlan (Natural Product Research, 2020)

Hydrological drought indexing approach in response to climate and anthropogenic activities - Waseem Muhammad; Shahid Muhammad; Noor Muhammad Khan; Chen Si (Theoretical and Applied Climatology, 2020)

Hydrogeochemical investigation of arsenic in drinking water of schools and age dependent risk assessment in Vehari District, Punjab Pakistan: a multivariate analysis - Behzad Murtaza; Humaira Nazeer; Natasha; Muhammad Amjad; Muhammad Imran; Muhammad Shahid; Noor S. Shah; Abu Bakr Umer Farooq; Muhammad Amjad; Ghulam Murtaza (Environmental Science and Pollution Research, 2020)

Compositional and health risk assessment of drinking water from health facilities of District Vehari, Pakistan - Behzad Murtaza; Natasha; Muhammad Amjad; Muhammad Shahid; Muhammad Imran; Noor Samad Shah; Ghulam Abbas; Muhammad Asif Naeem; Muhammad Amjad (Environmental Geochemistry and Health, 2020)

A new biochar from cotton stalks for As (V) removal from aqueous solutions: its improvement with H3PO4 and KOH - Munawar Hussain; Muhammad Imran; Ghulam Abbas; Muhammad Shahid; Muhammad Iqbal; Muhamamd Asif Naeem; Behzad Murtaza; Muhammad Amjad; Noor Samad Shah; Zia Ul Haq Khan; Azhar Ul Islam (Environmental Geochemistry and Health, 2020)

Selective cyclooxygenase-2 inhibitors: A review of recent chemical scaffolds with promising anti-inflammatory and COX-2 inhibitory activities - Noor-ul-Amin Mohsin; Muhammad Irfan (Medicinal Chemistry Research, 2020)

Selective and simultaneous detection of cadmium, lead and copper by tapioca-derived carbon dot–modified electrode - Musa Yahaya Pudza; Zurina Zainal Abidin; Suraya Abdul-Rashid; Faizah Md Yasin; Ahmad Shukri Muhammad Noor; Jaafar Abdullah (Environmental Science and Pollution Research, 2020)

Evaluation of the bioenergy potential of invasive Pennisetum purpureum through pyrolysis and thermogravimetric analysis - Md Sumon Reza; Shafi Noor Islam; Shammya Afroze; Muhammad S. Abu Bakar; Rahayu S. Sukri; Saidur Rahman; Abul K. Azad (Energy, Ecology and Environment, 2020)

Assessment of subsurface lithology, groundwater depth, and quality of UET Lahore, Pakistan, using electrical resistivity method - Zahid Mehmood; Noor Muhammad Khan; Shamsher Sadiq; Saeed-ullah Jan Mandokhail; Syed Zishan Ashiq (Arabian Journal of Geosciences, 2020)

Molecular characterization and phylogenetic analysis of Pantoea stewartii subspecies stewartii causing bronzing disease of jackfruit in Malaysia based on cps and hrp gene sequences - Rohaya Ibrahim; Noor Wahida Ismail-Suhaimy; Tan Shu-Qing; Siti Izera Ismail; Nuraizat Abidin; Mansor Hakiman; Daljit Singh Karam; Muhammad Saiful Ahmad-Hamdani; Mohd Termizi Yusof; Dzarifah Zulperi (Journal of Plant Pathology, 2020)

Dynamics of AB-DTPA-extractable Zn in high and low limed calcareous soils amended with biochar and farmyard and poultry manures - Abida Saleem; Dost Muhammad; Mumtaz Khan; Qudrat Ullah Khan; Muhammad Rizwan; Salma Shaheen; Hamza Noor; Shiza Gul; Muhammad Daud Khan; Shafaqat Ali (Arabian Journal of Geosciences, 2020)

Response of growth, antioxidant enzymes and root exudates production towards As stress in Pteris vittata and in Astragalus sinicus colonized by arbuscular mycorrhizal fungi - Liu Yizhu; Muhammad Imtiaz; Allah Ditta; Muhammad Shahid Rizwan; Muhammad Ashraf; Sajid Mehmood; Omar Aziz; Fathia Mubeen; Muhammad Ali; Nosheen Noor Elahi; Raina Ijaz; Sha Lele; et al. (Environmental Science and Pollution Research, 2020)

Cell membrane fatty acid and pigment composition of the psychrotolerant cyanobacterium Nodularia spumigena CHS1 isolated from Hopar glacier, Pakistan - Noor Hassan; Alexandre M. Anesio; Muhammad Rafiq; Jens Holtvoeth; Ian Bull; Christopher J. Williamson; Fariha Hasan (Extremophiles, 2020)

Modulation in growth, gas exchange, and antioxidant activities of salt-stressed rice (Oryza sativa L.) genotypes by zinc fertilization - Muhammad Jan; Muhammad Anwar-ul-Haq; Adnan Noor Shah; Muhammad Yousaf; Javaid Iqbal; Xiuling Li; Depeng Wang; Shah Fahad (Arabian Journal of Geosciences, 2019)

Physiological response of spinach to toxic heavy metal stress - Muhammad Zubair; Qudrat Ullah Khan; Nosheen Mirza; Rizwana Sarwar; Asghar Ali Khan; Mohammad Safdar Baloch; Shah Fahad; Adnan Noor Shah (Environmental Science and Pollution Research, 2019)

Selection of CMIP5 multi-model ensemble for the projection of spatial and temporal variability of rainfall in peninsular Malaysia - Muhammad Noor; Tarmizi bin Ismail; Shamsuddin Shahid; Kamal Ahmed; Eun-Sung Chung; Nadeem Nawaz (Theoretical and Applied Climatology, 2019)

Novel nonsense IL-12Rβ1 mutation associated with recurrent tuberculosis - Noor ul Akbar; Shahid Niaz Khan; Muhammad Usman Amin; Muhammad Ishfaq; Otavio Cabral-Marques; Lena F Schimke; Asif Iqbal; Ikram Ullah; Mubashir Hussain; Ijaz Ali; Nasar Khan; Nadia El Khawanky; et al. (Immunologic Research, 2019)

Synthesis of magnetite-based nanocomposites for effective removal of brilliant green dye from wastewater - Muhammad Imran; Azhar Ul Islam; Muhammad Adnan Tariq; Muhammad Hussnain Siddique; Noor Samad Shah; Zia Ul Haq Khan; Muhammad Amjad; Salah Ud Din; Ghulam Mustafa Shah; Muhammad Asif Naeem; Muhammad Nadeem; Muhammad Nawaz; et al. (Environmental Science and Pollution Research, 2019)

Health risk assessment of drinking arsenic-containing groundwater in Hasilpur, Pakistan: effect of sampling area, depth, and source - Riaz Ahmad Tabassum; Muhammad Shahid; Camille Dumat; Nabeel Khan Niazi; Sana Khalid; Noor Samad Shah; Muhammad Imran; Samina Khalid (Environmental Science and Pollution Research, 2019)

A multivariate analysis of physiological and antioxidant responses and health hazards of wheat under cadmium and lead stress - Behzad Murtaza; Faryal Naeem; Muhammad Shahid; Ghulam Abbas; Noor S. Shah; Muhammad Amjad; Hafiz Faiq Bakhat; Muhammad Imran; Nabeel Khan Niazi; Ghulam Murtaza (Environmental Science and Pollution Research, 2019)

Earthworms as plug flow reactors: a first-order kinetic study on the gut of the vermicomposting earthworm Eudrilus eugeniae - Katheem Kiyasudeen; Mahamad Hakimi Ibrahim; Syahidah Akmal Muhammad; Sultan Ahmed Ismail; Fadzil Noor Gonawan; Mark Harris Zuknik (Environmental Science and Pollution Research, 2018)

Concentrations, dietary exposure, and human health risk assessment of heavy metals in market vegetables of Peshawar, Pakistan - Mehboob Alam; Maaz Khan; Anwarzeb Khan; Shah Zeb; Muhammad Amjad Khan; Noor ul Amin; Muhammad Sajid; Abdul Mateen Khattak (Environmental Monitoring and Assessment, 2018)

Biochemical and structural characterization of a novel cold-active esterase-like protein from the psychrophilic yeast Glaciozyma antarctica - Noor Haza Fazlin Hashim; Nor Muhammad Mahadi; Rosli Md Illias; Shevin Rizal Feroz; Farah Diba Abu Bakar; Abdul Munir Abdul Murad (Extremophiles, 2018)

Potential harmful elements in coal dust and human health risk assessment near the mining areas in Cherat, Pakistan - Muhammad Ishtiaq; Noor Jehan; Said Akbar Khan; Said Muhammad; Umar Saddique; Bushra Iftikhar; Zahidullah (Environmental Science and Pollution Research, 2018)

Ethnoveterinary health management practices using medicinal plants in South Asia – a review - Shanoo Suroowan; Faisal Javeed; Mushtaq Ahmad; Muhammad Zafar; Mehwish Jamil Noor; Sadaf Kayani; Ali Javed; Mohamad Fawzi Mahomoodally (Veterinary Research Communications, 2017)

Retraction Note to: Estimation of Anticipated Performance Index and Air Pollution Tolerance Index and of vegetation around the marble industrial areas of Potwar region: bioindicators of plant pollution response - Mehwish Jamil Noor; Shazia Sultana; Sonia Fatima; Mushtaq Ahmad; Muhammad Zafar; Maliha Sarfraz; Masour A. Balkhyour; Sher Zaman Safi; Muhammad Aqeel Ashraf (Environmental Geochemistry and Health, 2017)

Exogenous application of plant growth regulators (PGRs) induces chilling tolerance in short-duration hybrid maize - Muhammad Ahmed Waqas; Imran Khan; Muhammad Javaid Akhter; Mehmood Ali Noor; Umair Ashraf (Environmental Science and Pollution Research, 2017)

Soil compaction effects on soil health and cropproductivity: an overview - Adnan Noor Shah; Mohsin Tanveer; Babar Shahzad; Guozheng Yang; Shah Fahad; Saif Ali; Muhammad Adnan Bukhari; Shahbaz Atta Tung; Abdul Hafeez; Biangkham Souliyanonh (Environmental Science and Pollution Research, 2017)

Generating Synthetic Rainfall Total Using Multivariate Skew-t and Checkerboard Copula of Maximum Entropy - Noor Fadhilah Ahmad Radi; Roslinazairimah Zakaria; Julia Piantadosi; John Boland; Wan Zawiah Wan Zin; Muhammad Az-zuhri Azman (Water Resources Management, 2017)

Number of pegs influence focal stress distributions and micromotion in glenoid implants: a finite element study - Abdul Hadi Abdul Wahab; Mohammed Rafiq Abdul Kadir; Muhammad Noor Harun; Tunku Kamarul; Ardiyansyah Syahrom (Medical & Biological Engineering & Computing, 2017)

Optimizing the phosphorus use in cotton by using CSM-CROPGRO-cotton model for semi-arid climate of Vehari-Punjab, Pakistan - Asad Amin; Wajid Nasim; Muhammad Mubeen; Muhammad Nadeem; Liaqat Ali; Hafiz Mohkum Hammad; Syeda Refat Sultana; Khawar Jabran; M. Habib ur Rehman; Shakeel Ahmad; Muhammad Awais; Atta Rasool; et al. (Environmental Science and Pollution Research, 2017)

Nitrogen fertilization and conservation tillage: a review on growth, yield, and greenhouse gas emissions in cotton - Adnan Noor Shah; Javaid Iqbal; Mohsin Tanveer; Guozheng Yang; Waseem Hassan; Shah Fahad; Muhammad Yousaf; Yingying Wu (Environmental Science and Pollution Research, 2017)

Modelling the kinetics of hexavalent molybdenum (Mo6+) reduction by the Serratia sp. strain MIE2 in batch culture - Mohd Izuan Effendi Halmi; Siti Rozaimah Sheikh Abdullah; Wan Lutfi Wan Johari; Mohd Shukuri Muhammad Ali; Noor Azmi Shaharuddin; Ariff Khalid; Mohd Yunus Shukor (Rendiconti Lincei. Scienze Fisiche e Naturali, 2016)

The combined treatment of Mn and Al alleviates the toxicity of Al or Mn stress alone in barley - Noor Muhammad; Shengguan Cai; Jawad Munawar Shah; Guoping Zhang (Acta Physiologiae Plantarum, 2016)

Allelopathic potential of oil seed crops in production of crops: a review - Adnan Noor Shah; Javaid Iqbal; Abid Ullah; Guozheng Yang; Muhammad Yousaf; Shah Fahad; Mohsin Tanveer; Waseem Hassan; Shahbaz Atta Tung; Leishan Wang; Aziz Khan; Yingying Wu (Environmental Science and Pollution Research, 2016)

RETRACTED ARTICLE: Floristic and ethnoecological diversity in various habitats of a semi-arid area in the Chakwal district (Pakistan), with special emphasis on medicinal plants - Mehwish Jamil Noor; Mushtaq Ahmad; Muhammad Zafar; Maliha Sarfraz; Ismail Yusoff; Yatimah Alias; Muhammad Aqeel Ashraf (Plant Ecology, 2016)

Psychrophilic and psychrotrophic fungi: a comprehensive review - Noor Hassan; Muhammad Rafiq; Muhammad Hayat; Aamer Ali Shah; Fariha Hasan (Reviews in Environmental Science and Bio/Technology, 2016)

Biofunctional properties of Eruca sativa Miller (rocket salad) hydroalcoholic extract - Khushbakht Sultan; Muhammad Zakir; Haroon Khan; Abdur Rauf; Noor Ul Akber; Murad Ali Khan (Natural Product Research, 2016)

Alleviation of lead-induced physiological, metabolic, and ultramorphological changes in leaves of upland cotton through glutathione - Mumtaz Khan; M. K. Daud; Ali Basharat; Muhammad Jamil Khan; Azizullah Azizullah; Niaz Muhammad; Noor Muhammad; Zia ur Rehman; Shui Jin Zhu (Environmental Science and Pollution Research, 2016)

A review of the pollen analysis of South Asian honey to identify the bee floras of the region - Mehwish Jamil Noor; Mushtaq Ahmad; Muhammad Aqeel Ashraf; Muhammad Zafar; Shazia Sultana (Palynology, 2016)

The battle of health with environmental evils of Asian countries: promises to keep - Muhammad Imran Qureshi; Noor Ullah Khan; Amran Md. Rasli; Khalid Zaman (Environmental Science and Pollution Research, 2015)

Petrographic and structural controls on geotechnical feasibility of dam sites: implications from investigation at Sher Dara area (Swabi), north-western Pakistan - Yasir Shaheen Khalil; Mohammad Arif; Hasnain Ali Bangash; Muhammad Sajid; Noor Muhammad (Arabian Journal of Geosciences, 2015)

RETRACTED ARTICLE: Estimation of Anticipated Performance Index and Air Pollution Tolerance Index and of vegetation around the marble industrial areas of Potwar region: bioindicators of plant pollution response - Mehwish Jamil Noor; Shazia Sultana; Sonia Fatima; Mushtaq Ahmad; Muhammad Zafar; Maliha Sarfraz; Masour A. Balkhyour; Sher Zaman Safi; Muhammad Aqeel Ashraf (Environmental Geochemistry and Health, 2015)

Optimization of Multiple Reservoirs Operation with Consideration to Sediment Evacuation - Muhammad Usman Rashid; Abdul Sattar Shakir; Noor Muhammad Khan; Abid Latif; Muhammad Mubashir Qureshi (Water Resources Management, 2015)

Molecular cloning, expression and characterisation of Afp4, an antifreeze protein from Glaciozyma antarctica - Noor Haza Fazlin Hashim; Suhaila Sulaiman; Farah Diba Abu Bakar; Rosli Md Illias; Hidehisa Kawahara; Nazalan Najimudin; Nor Muhammad Mahadi; Abdul Munir Abdul Murad (Polar Biology, 2014)

Molecular Characterization of Chenopodium album Chloroplast Small Heat Shock Protein and Its Expression in Response to Different Abiotic Stresses - Noor Ul Haq; Muhammad Ammar; Asghari Bano; Dawn S. Luthe; Scott A. Heckathorn; Samina N. Shakeel (Plant Molecular Biology Reporter, 2013)

Development of a Polygonum minus cell suspension culture system and analysis of secondary metabolites enhanced by elicitation - Muhammad Faizan A. Shukor; Ismanizan Ismail; Zamri Zainal; Normah Mohd Noor (Acta Physiologiae Plantarum, 2013)

Characterization of Afp1, an antifreeze protein from the psychrophilic yeast Glaciozyma antarctica PI12 - Noor Haza Fazlin Hashim; Izwan Bharudin; Douglas Law Sie Nguong; Sakura Higa; Farah Diba Abu Bakar; Sheila Nathan; Amir Rabu; Hidehisa Kawahara; Rosli Md. Illias; Nazalan Najimudin; Nor Muhammad Mahadi; Abdul Munir Abdul Murad (Extremophiles, 2013)

Prevalence of TP53 germ line mutations in young Pakistani breast cancer patients - Muhammad U. Rashid; Sidra Gull; Kashif Asghar; Noor Muhammad; Asim Amin; Ute Hamann (Familial Cancer, 2012)

A mutant l-asparaginase II signal peptide improves the secretion of recombinant cyclodextrin glucanotransferase and the viability of Escherichia coli - Noor Faizah Ismail; Salehhuddin Hamdan; Nor Muhammad Mahadi; Abdul Munir Abdul Murad; Amir Rabu; Farah Diba Abu Bakar; Peter Klappa; Rosli Md. Illias (Biotechnology Letters, 2011)